Resin composition, resin film, metal-clad laminate, and printed wiring board
By adding liquid crystal polymer filler with anisotropy shape and a base material polymer to the resin, the problems of high dielectric loss tangent and large thermal expansion coefficient in high frequency signal transmission of the circuit substrate material insulating resin layer are solved, and excellent dielectric characteristics and dimensional stability are achieved.
Patent Information
- Application Number
- CN202510181465.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-23
- Filing Date
- 2021-06-10
- Publication Date
- 2025-04-25
AI Technical Summary
The insulating resin layer of the existing circuit substrate material has a high dielectric loss tangent in high-frequency signal transmission, resulting in large transmission losses and large thermal expansion coefficients, which affects dimensional stability.
By mixing a liquid crystal polymer filler with anisotropy in the resin, the formed resin film has excellent dielectric properties and dimensional stability in combination with the fixation of the base material polymer.
It is achieved without damaging the physical properties of the resin film, reducing high-frequency signal transmission losses and improving dimensional stability, and is suitable for use as circuit substrate materials such as FPC.
Smart Images

Figure BDA0005277165320000031 
Figure BDA0005277165320000081 
Figure BDA0005277165320000111
Abstract
Description
[0001] This invention is a divisional application of the invention patent application with application number 202110647769.2 filed on June 10, 2021 and invention name “Printed Wiring Board”. Technical Field
[0002] The present invention relates to, for example, a resin composition, a resin film, a metal-clad laminate, and a printed wiring board that are effectively used as a circuit board material. Background Art
[0003] Flexible circuit boards (Flexible Printed Circuit Boards, FPCs) can be installed three-dimensionally and at high density even in a limited space, so their use has expanded to the wiring or cables, connectors and other parts of the movable parts of electronic devices, and are installed on equipment in many fields. With this, the environment in which FPCs are used is becoming increasingly diverse, and the required performance is also getting higher and higher. For example, in information processing or information communication, efforts have been made to increase the transmission frequency in order to transmit and process large amounts of information. For circuit boards, there is also a strong demand to reduce transmission losses by improving the dielectric properties of the insulating resin layer.
[0004] As one of the methods for improving the dielectric properties of the insulating resin layer, research is being conducted to make the matrix itself of the insulating resin layer contain a resin with a low dielectric loss tangent. For example, liquid crystal polymer is a resin characterized by low dielectric constant and low dielectric loss tangent. By using it as a matrix, the dielectric properties of the insulating resin layer can be greatly improved. However, the film with liquid crystal polymer as the matrix has the problem of low heat resistance and low adhesion to metal foil, and cannot meet all the characteristics required as a circuit substrate material.
[0005] Also known as resin materials having excellent dielectric properties are fluororesins, polyolefins, polystyrenes, polyesters, etc. However, these resins have a problem that their linear thermal expansion coefficients are very large, and when used in insulating resin layers, the dimensional stability of the circuit board is significantly impaired.
[0006] As another method, it has been proposed to compound a filler or a nonwoven fabric that can reduce the dielectric constant or dielectric loss tangent on a base material constituting the insulating resin layer (Patent Documents 1 to 3).
[0007] Patent Document 1 proposes to mix liquid crystal polymer particles in a thermoplastic resin or a thermosetting resin. However, Patent Document 1 does not study the shape of the liquid crystal polymer particles.
[0008] Patent Document 2 proposes to add a polytetrafluoroethylene microparticle filler having a low dielectric constant to a continuous phase containing para-oriented aromatic polyamide to achieve a low dielectric constant. However, Patent Document 2 does not study the control of the dielectric loss tangent which is closely related to the transmission loss of high-frequency signals. In addition, the aromatic polyamide short fibers are added together with the polytetrafluoroethylene microparticle filler for the purpose of improving mechanical properties, resulting in a complex composition.
[0009] In Patent Document 3, in order to achieve low water absorption, low dielectric constant, and low dielectric loss tangent while taking into account the thinning, low cost, laser processability, copper migration resistance, etc. of the printed wiring board, it is proposed to reinforce the matrix resin including bismaleimide triazine resin or epoxy resin by a non-woven fabric including molten liquid crystalline polyester fiber. However, Patent Document 3 does not envision the response to high-frequency signal transmission above 20 GHz, which will become increasingly important in the future, and the research on reducing the dielectric loss tangent, which is closely related to the transmission loss of high-frequency signals, is insufficient.
[0010] On the other hand, regarding the control of the thermal expansion coefficient of the resin film, for example, in Non-Patent Document 1, a study is being conducted on compounding an inorganic filler such as carbon fiber on an epoxy resin. However, there is a problem that the addition of the inorganic filler reduces the flexibility or toughness of the resin film, thereby impairing the physical properties required as a circuit board material.
[0011] It is well known that the method of improving functionality by adding fillers to the insulating resin layer for compounding is not limited to the improvement of dielectric properties. For example, in Patent Document 4, it is proposed to obtain an insulating resin with excellent mechanical strength and low thermal expansion coefficient by adding aramid fiber or glass fiber to injection-molded epoxy resin. In Patent Document 4, it is recorded that by further adding particulate fillers, the anisotropy of the thermal expansion coefficient peculiar to fibrous fillers can be eliminated, but no research is conducted on dielectric properties or flexibility.
[0012] In addition, Patent Document 5 proposes to prepare a high-strength molding material with less anisotropy of thermal expansion coefficient by adding fibrous fillers and spherical fillers to epoxy resin. However, in Patent Document 5, since inorganic fibers are used, it is difficult to mold into a flexible resin film, and no research is conducted on the improvement of dielectric properties.
[0013] [Prior art literature]
[0014] [Patent Document]
[0015] [Patent Document 1] Japanese Patent No. 6295013
[0016] [Patent Document 2] Japanese Patent Application Laid-Open No. 10-338809
[0017] [Patent Document 3] Japanese Patent Publication No. 2002-64254
[0018] [Patent Document 4] Japanese Patent Application Laid-Open No. 11-273456
[0019] [Patent Document 5] Japanese Patent No. 6547277
[0020] [Non-patent literature]
[0021] [Non-patent document 1] Proceedings of the Japan Society of Mechanical Engineers (Edition A) Vol. 74 No. 740 (2008-4), Paper No. 07-0770 Summary of the invention
[0022] [Problems to be solved by the invention]
[0023] Therefore, an object of the present invention is to provide a resin film that achieves both dielectric properties and dimensional stability without sacrificing physical properties such as flexibility and toughness.
[0024] [Technical means to solve the problem]
[0025] As a result of intensive studies to solve the above problems, the inventors found that by blending a liquid crystal polymer filler having shape anisotropy into a resin serving as a matrix material, both dielectric properties and dimensional stability can be improved without impairing the physical properties of the resin film, thereby completing the present invention.
[0026] That is, the resin film of the present invention contains the following components (A) and (B):
[0027] (A) a liquid crystal polymer filler having anisotropic shape and wherein X / Y is 2.5 or more when the average length of the major axis is X and the average length of the shortest minor axis among axes orthogonal to the major axis is Y; and
[0028] (B) A matrix polymer covers and fixes the component (A).
[0029] The resin film of the present invention preferably satisfies the following conditions (i) to (iii):
[0030] (i) the absolute value of the average linear thermal expansion coefficient from 250°C to 100°C is 50 ppm / K or less,
[0031] (ii) the dielectric loss tangent at 20 GHz under an environment of 23°C and 50% RH is less than 0.003, and
[0032] (iii) The water absorption rate when immersed in pure water at 23° C. for 24 hours is 0.2% by weight or less.
[0033] In the resin film of the present invention, the component (B) may be the organic component with the largest content in the composition after removing the component (A), and may be one or more selected from the group consisting of fluororesins, polyolefins, polystyrenes, polyimides, polyamides, polyethers, polyether ketones and polyesters.
[0034] In the resin film of the present invention, the liquid crystal polymer filler may have anisotropy in molecular orientation, and the difference between the maximum and minimum values of the average linear thermal expansion coefficient measured in the three axial directions including the major axis, the minor axis and the intermediate axis which are orthogonal to each other in the outer shape is greater than 30 ppm / K.
[0035] In the resin film of the present invention, the melting point of the liquid crystal polymer filler may be 290° C. or higher.
[0036] In the resin film of the present invention, the average length Y of the minor axis of the liquid crystal polymer filler may be less than 200 μm.
[0037] In the resin film of the present invention, the dielectric loss tangent of the liquid crystal polymer filler at 20 GHz under an environment of 23° C. and 50% RH may be 0.002 or less.
[0038] In the resin film of the present invention, the liquid crystal polymer constituting the component (A) may have a polyester structure.
[0039] In the resin film of the present invention, the content of the component (A) may be in the range of 2% by weight or more and 80% by weight or less relative to the total amount of the component (A) and the component (B).
[0040] In the resin film of the present invention, the component (B) may be a polymer using a diamine component as a raw material or a curing agent, wherein the diamine component in the polymer contains a dimer diamine composition having as a main component a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl or amino groups in an amount of 30 mol % or more relative to all diamine components.
[0041] In the resin film of the present invention, the (B) component may be a polyimide obtained by reacting a tetracarboxylic anhydride component and a diamine component as raw materials, and the polyimide may contain a total of 50 mol parts or more of tetracarboxylic anhydride represented by the following general formula (1) and / or general formula (2) relative to 100 mol parts of the tetracarboxylic anhydride component.
[0042] [Chemistry 1]
[0043]
[0044] In the general formula (1), X represents a single bond or a divalent group selected from the following formula; in the general formula (2), the cyclic part represented by Y represents a cyclic saturated hydrocarbon group selected from a four-membered ring, a five-membered ring, a six-membered ring, a seven-membered ring or an eight-membered ring.
[0045] [Chemistry 2]
[0046] -CO-, -SO2-, -O-,
[0047] -C(CF3)2-,
[0048] -COO- or -COO-Z-OCO-
[0049] In the above formula, Z represents -C6H4-, -(CH2)n- or -CH2-CH(-OC(=O)-CH3)-CH2-, and n represents an integer of 1 to 20.
[0050] The resin film of the present invention may be an adhesive sheet.
[0051] The method for producing a resin film of the present invention is the method for producing a resin film according to any one of the above items, comprising:
[0052] A step of separately preparing a first polymer as a liquid crystal polymer and a second polymer that is the same as or different from the first polymer;
[0053] a step of orienting the molecules of the first polymer; and
[0054] A step of using the first polymer as a filler to form a composite with the second polymer.
[0055] The resin composition of the present invention contains the following components (A) and (B):
[0056] (A) a liquid crystal polymer filler having anisotropic shape and wherein X / Y is 2.5 or more when the average length of the major axis is X and the average length of the shortest minor axis among axes orthogonal to the major axis is Y; and
[0057] (B) Matrix polymer.
[0058] In the resin composition of the present invention, the component (A) may be a fibrous liquid crystal polymer filler. The resin composition of the present invention may further contain the following component (C):
[0059] (C) A particulate metal oxide filler and / or a particulate thermoplastic resin filler.
[0060] In the resin composition of the present invention, the total content of the fillers of the (A) component and the (C) component may be in the range of 10% to 90% by volume, and the content of the (B) component may be in the range of 10% to 90% by volume, relative to the content of the solid content in the resin composition.
[0061] In the resin composition of the present invention, the ratio L / D of the average length L of the major axis of the fibrous liquid crystal polymer filler of the component (A) to the average diameter D of the minor axis perpendicular to the major axis may be 2.5 or more.
[0062] In the resin composition of the present invention, the fibrous liquid crystal polymer filler of the component (A) may have an average length L of the major axis in the range of 0.1 mm to 5 mm, and an average diameter D of the minor axis in the range of 5 μm to 50 μm.
[0063] In the resin composition of the present invention, the fibrous liquid crystal polymer filler of the component (A) may have a melting point of 290° C. or higher.
[0064] In the resin composition of the present invention, the content of the fibrous liquid crystal polymer filler as the component (A) may be in the range of 5% by volume to 60% by volume relative to the content of the solid content in the resin composition.
[0065] In the resin composition of the present invention, the volume average particle size D of the particulate metal oxide filler and the particulate thermoplastic resin filler of the component (C) is 50 It can be in the range of 1 μm to 100 μm.
[0066] In the resin composition of the present invention, the particulate thermoplastic resin filler of the component (C) may be particles of at least one selected from the group consisting of thermoplastic polyimide, liquid crystal polymer, and fluororesin.
[0067] In the resin composition of the present invention, the particulate metal oxide filler of the component (C) may be silica particles in which the ratio of the total area of the peaks originating from the white silica crystal phase and the quartz crystal phase in the range of 2θ=10° to 90° of the X-ray diffraction analysis spectrum using CuKα rays to the total area of all peaks originating from SiO2 is 20 weight % or more.
[0068] In the resin composition of the present invention, the content of the component (C) may be in the range of 20% by volume to 80% by volume relative to the content of the solid content in the resin composition.
[0069] In the resin composition of the present invention, the ratio of the content of the fibrous liquid crystal polymer filler of the component (A) to the content of the component (C) [component (A) / component (C)] may be in the range of 0.1 to 10 on a volume basis.
[0070] In the resin composition of the present invention, the average diameter D of the minor axis of the fibrous liquid crystal polymer filler of the component (A) is equal to the volume average particle diameter D of the particulate metal oxide filler or particulate thermoplastic resin filler of the component (C). 50 The ratio [D / D 50 ] can be in the range of 1 to 50.
[0071] In the resin composition of the present invention, the average length L of the major axis of the fibrous liquid crystal polymer filler of the component (A) is equal to the volume average particle size D of the particulate metal oxide filler or particulate thermoplastic resin filler of the component (C). 50 The ratio [L / D 50 ] can be in the range of 10 to 1000.
[0072] In the resin composition of the present invention, the component (B) may be at least one selected from thermoplastic polyimide, liquid crystal polymer and fluororesin.
[0073] In the resin composition of the present invention, the component (B) may be a polyimide using a diamine component as a raw material, wherein the diamine component in the polyimide contains a dimer diamine composition having as a main component a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl or amino groups in an amount of 30 mol % or more relative to all diamine components.
[0074] The resin film of the present invention is a resin film having a single layer or a plurality of resin layers, and at least one layer of the resin layers is a filler-containing resin layer formed using any one of the above-mentioned resin compositions.
[0075] In the resin film of the present invention, after the filler-containing resin layer is conditioned at a constant temperature and humidity of 23°C and 50% RH for 24 hours, the relative dielectric constant at 10 GHz measured by a Split Post Dielectric Resonator (SPDR) can be less than 3, and the dielectric loss tangent can be less than 0.003.
[0076] In the resin film of the present invention, the absolute value of the average coefficient of thermal expansion (CTE) of the filler-containing resin layer in the machine direction (MD) at 10°C to 20°C may be 50 ppm / K or less, and the absolute value of the average coefficient of thermal expansion (CTE) in the transverse direction (TD) may be 100 ppm / K or less.
[0077] The metal-clad laminate of the present invention is a metal-clad laminate comprising a single-layer or multi-layer insulating resin layer and a metal layer laminated on at least one side of the insulating resin layer, wherein
[0078] At least one layer constituting the insulating resin layer includes any one of the above-described resin films.
[0079] The printed wiring board of the present invention is a printed wiring board comprising a single-layer or multi-layer insulating resin layer and a circuit wiring layer laminated on at least one side of the insulating resin layer, wherein
[0080] At least one layer constituting the insulating resin layer includes any one of the above-described resin films.
[0081] [Effects of the Invention]
[0082] The resin film of the present invention contains a liquid crystal polymer filler having anisotropic shape, and therefore has excellent dielectric properties and dimensional stability without compromising the physical properties such as flexibility or toughness required for the resin film. The resin film of the present invention effectively reduces the transmission loss of high-frequency signals (e.g., high-frequency signals above 10 GHz, especially above 20 GHz) through low dielectric loss tangent, and has excellent dimensional stability, so it can be suitably used as a circuit substrate material such as FPC in various electronic devices. DETAILED DESCRIPTION
[0083] Hereinafter, embodiments of the present invention will be described.
[0084] The resin film according to one embodiment of the present invention contains the following components (A) and (B):
[0085] (A) a liquid crystal polymer filler having anisotropic shape and wherein X / Y is 2.5 or more when the average length of the major axis is X and the average length of the shortest minor axis among axes orthogonal to the major axis is Y; and
[0086] (B) A matrix polymer covers and fixes the component (A).
[0087] Here, the liquid crystal polymer filler with X / Y of 2.5 or more also includes a fibrous liquid crystal polymer filler (hereinafter, the same applies).
[0088] Furthermore, the resin composition according to one embodiment of the present invention contains the following components (A) and (B):
[0089] (A) a liquid crystal polymer filler having anisotropic shape and wherein X / Y is 2.5 or more when the average length of the major axis is X and the average length of the shortest minor axis among axes orthogonal to the major axis is Y; and
[0090] (B) Matrix polymer.
[0091] Next, a first embodiment and a second embodiment are listed as preferred embodiments of the present invention, and a metal-clad laminate and a printed wiring board using these embodiments are described.
[0092] {First embodiment}
[0093] [Resin film]
[0094] The resin film of the present embodiment contains the following components (A) and (B):
[0095] (A) a liquid crystal polymer filler having anisotropic shape and wherein X / Y is 2.5 or more when the average length of the major axis is X and the average length of the shortest minor axis among axes orthogonal to the major axis is Y; and
[0096] (B) A matrix polymer covers and fixes the component (A).
[0097] Here, the components (A) and (B) may be the same type of polymers, and include, for example, a combination in which the component (A) is a liquid crystalline polyester and the component (B) is a non-liquid crystalline polyester.
[0098] If the resin film as a whole satisfies conditions (i) to (iii), the resin film of the present embodiment may be a single layer or may include multiple layers. For example, the resin film as a whole may be a layer containing components (A) and (B), or may include any resin layer other than the layer containing components (A) and (B). However, the layer containing components (A) and (B) is preferably the main layer of the resin film. Here, the "main layer" refers to a layer having a thickness exceeding 50% relative to the overall thickness of the resin film.
[0099] In addition, the resin film can be used as an adhesive layer to constitute a part of the insulating resin layer, or can be used as a bonding sheet in the state of a film. Here, "bonding sheet" refers to a material used for the purpose of bonding films to each other, a film to metal, and metal to metal. Its use form is not limited to lamination in the state of a film, for example, it can also be applied as a varnish as an adhesive layer and hardened.
[0100] [(A) component: liquid crystal polymer filler]
[0101] The liquid crystal polymer (Liquid Crystal Polymer) constituting the liquid crystal polymer filler of component (A) is a resin that exhibits liquid crystal properties when melted, and may be a wholly aromatic liquid crystal polymer or a semi-aromatic liquid crystal polymer. The liquid crystal polymer filler of component (A) has shape anisotropy. The shape anisotropy of the present invention refers to the ratio (X / Y) of the average length of the major axis (X) of the liquid crystal polymer filler to the average length of the minor axis (Y) being 2.5 or more. Here, when a virtual cuboid circumscribed to the liquid crystal polymer filler in a linearly extending state is assumed, the length of the shortest of the three mutually perpendicular sides of the cuboid is set as the length of the minor axis, the length of the longest side is set as the length of the major axis, and the length of the remaining side is set as the length of the intermediate axis.
[0102] Furthermore, in the liquid crystal polymer filler, X / Y is preferably 4.5 or more, more preferably X / Y is 15.0 or more, and further preferably X / Y is 30.0 or more. When X / Y is less than 2.5, the liquid crystal polymer filler is easily arranged in a disordered manner in the resin film, thereby reducing the CTE improvement effect. In addition, the liquid crystal polymer fillers are easily agglomerated with each other, and other undesirable conditions are exhibited.
[0103] The average length (Y) of the minor axis of the liquid crystal polymer filler is preferably within a range of 0.1 μm or more and less than 200 μm, and more preferably within a range of 1 μm or more and 150 μm or less. If the average length (Y) of the minor axis is within the above range, the surface smoothness when forming the resin film will not deteriorate, and a resin film with good appearance can be obtained.
[0104] The average length (X) of the major axis of the liquid crystal polymer filler can be appropriately selected according to the composite method of the liquid crystal polymer filler and the (B) component. For example, if the method is to disperse the liquid crystal polymer filler in the (B) component, it is preferably within the range of 0.5 μm or more and 5000 μm or less, and more preferably within the range of 5 μm or more and 2500 μm or less. In addition, for example, if the method is to impregnate the (B) component in the liquid crystal polymer filler, it is preferably 1 cm or more, and more preferably 3 cm or more. If the average length (X) of the major axis is within the range, the handleability will not be impaired, and the surface smoothness when forming the resin film will not deteriorate, so that a resin film with good appearance can be obtained.
[0105] In the liquid crystal polymer filler, the liquid crystal polymer molecular chain is preferably strongly oriented in the long axis direction of the filler, and the result is preferably that the thermal expansion coefficient in the shortest axis direction (Y axis direction) in the axis orthogonal to the long axis direction (X axis direction) has anisotropy. In particular, when the thermal expansion coefficient in the X axis direction is negative, the shrinkage relative to the X axis direction is greater than the elongation relative to the Y axis direction, which can reduce the CTE of the resin film, and is therefore more preferred. From the same point of view, by the orientation of the molecular chain, the difference between the maximum and minimum values in the average linear thermal expansion coefficient measured in the three axis directions of the long axis, short axis and intermediate axis orthogonal to each other in the outer shape of the liquid crystal polymer filler is preferably 30ppm / K or more, more preferably 50ppm / K or more. In addition, the minimum value is preferably less than 50ppm / K, more preferably less than 20ppm / K, and further preferably less than 5ppm / K.
[0106] Various methods of manufacturing liquid crystal polymer fillers with anisotropy of thermal expansion coefficient can be considered. As an example, there is a manufacturing method of applying shear force to a polymer with a main chain having a rigid structure and not having a rigid substituent or a bulky structure in the side chain. Thus, a filler with high orientation in the shear direction can be obtained. As an example of a polymer with a main chain having a rigid structure and not having a rigid substituent or a bulky structure in the side chain, polyesters, aromatic polyimides, aromatic polyamides (another name: aromatic polyamides), aromatic polyamide-imides, and fluororesins in which there are no multiple phenyl groups, liquid crystal original groups, saturated or unsaturated aliphatic chains or alicyclic structures with a carbon number exceeding 6 on the side chain can be listed. With respect to the dielectric properties of the filler, flame retardancy, thermal stability in the circuit substrate manufacturing process, hygroscopicity, and CTE, it is preferred to use aromatic polyesters. However, in the present invention, polyarylate is regarded as one of polyesters.
[0107] The liquid crystal polymer is not particularly limited, but is preferably a substance having a polyester structure such as a conventional thermotropic liquid crystal polyester or polyester amide derived from compounds classified into the following (1) to (4) and derivatives thereof.
[0108] (1) Aromatic or aliphatic dihydroxy compounds
[0109] (2) Aromatic or aliphatic dicarboxylic acids
[0110] (3) Aromatic hydroxycarboxylic acid
[0111] (4) Aromatic diamines, aromatic hydroxylamines or aromatic aminocarboxylic acids
[0112] As a representative example of a liquid crystal polymer obtained from these raw material compounds, a copolymer having a combination of two or more structural units selected from the following formulas (a) to (n), and containing any one of the structural units represented by formula (a) or formula (e), is preferred, and a copolymer containing the structural unit represented by formula (a) and the structural unit represented by formula (e) is particularly preferred. In addition, as the more aromatic rings in the liquid crystal polymer, the more effects of improving dielectric properties and flame retardancy can be expected, it is preferred to contain an aromatic dihydroxy compound as the (1) and contain an aromatic dicarboxylic acid as the (2).
[0113] [Chemistry 3]
[0114]
[0115] As a manufacturing method for applying shear force, there are various methods such as melt spinning, melt extrusion, solution casting method, and casting method. However, in order to effectively orient the liquid crystal polymer molecules, it is preferable to form through a melting step and an extrusion step. In particular, it is preferable to set the maximum shear rate u during extrusion obtained by the following formula to preferably 10 2 sec -1 More than 10 4 sec -1 above.
[0116] u=4Q / {π×(d / 2) 3}
[0117] [Wherein, Q represents the polymer discharge rate per unit time through the extrusion nozzle cross section (cm 3 / sec), d represents the length (cm) of the shortest diameter of the extrusion nozzle cross section, for example, in the case of a circular extrusion nozzle such as a tubular nozzle or a fine hole, it is set to its diameter (cm).]
[0118] When the maximum shear rate u is set as described above, the liquid crystal polymer molecules are sufficiently oriented, and the controllability of the CTE when the liquid crystal polymer is used as a filler can be easily obtained.
[0119] In particular, by ejecting the resin from fine holes, liquid crystal polymer fibers in which liquid crystal polymer molecules are strongly oriented in the long axis direction can be obtained. The fine holes are, for example, holes with a die opening diameter of 1 mm or less, more preferably 0.5 mm or less.
[0120] The obtained fiber can also be set as a combination of multiple materials. As a combination, twisted yarn, fabric, knitted fabric, non-woven fabric can be exemplified. The combination can also be subdivided by cutting, crushing, etc. In addition, it can also be set as a coagulant formed by combining multiple fillers showing shape anisotropy. For example, a coagulant can also be made by heating or chemical action. The coagulant can also be subdivided by cutting, crushing, etc. In addition, regarding the combination or coagulant, it is not their overall shape, as long as the shape anisotropy can be grasped in the state of the fiber.
[0121] For example, by bundling the liquid crystal polymer fibers produced by the method and cutting them into a predetermined length, a liquid crystal polymer filler in the form of short fibers (also referred to as short fibers or cut fibers) can be obtained. Furthermore, a ground fiber filler can be produced by pulverizing. At this time, the fibers can be frozen, and the liquid crystal polymer filler can be efficiently subdivided by freezing.
[0122] Alternatively, the liquid crystal polymer filler may be produced by pulverizing a molded product having an increased degree of orientation of liquid crystal polymer molecules instead of forming the product into fibers. In this case, the pulverization step may be repeated multiple times, and classification using wind power, buoyancy, or a sieve may also be performed.
[0123] As specific shapes of liquid crystal polymer fillers, for example, the above-mentioned fibrous (including needle-shaped), plate-shaped, etc. can be cited. As plate-shaped, disc-shaped, flat, flat, flake-shaped, scaly, short strips, etc. can be exemplified. In addition, the cross-sectional shape of the liquid crystal polymer filler is not limited to a circle, and can also be a star-shaped or flower-shaped, cross-shaped, or hollow. By changing the cross-sectional shape of the liquid crystal polymer filler, the surface area of the liquid crystal polymer filler can be adjusted to control the adhesion with the polyimide or the viscosity of the resin solution.
[0124] In addition, the shape of the liquid crystal polymer filler may be deformed in the resin film. For example, by stretching a resin film containing a spherical or amorphous liquid crystal polymer filler, the liquid crystal polymer filler may exhibit shape anisotropy in the resin film.
[0125] For the purpose of improving dispersibility or adhesion with (B) component, liquid crystal polymer filler can also be subjected to surface modification. As surface modification, for example, plasma treatment, coating treatment, etc. can be cited. In addition, liquid crystal polymer filler can also be a multilayer structure or a core-sheath structure. As a multilayer structure, for example, a hollow liquid crystal polymer filler or a porous liquid crystal polymer filler is preferably used, and as a core-sheath structure, for example, a core part is preferably a liquid crystal polymer and a sheath part is a resin with high adhesion with (B) component. As a resin with high adhesion with (B) component, for example, thermoplastic resins such as polyimide, polyamide, perfluoroalkoxy fluorine resin (perfluoroalkoxy alkane (perfluoroalkoxy alkane, PFA)), polyolefin are preferably used.
[0126] Liquid crystal polymer has very excellent dielectric properties. By using it as a filler for deployment, the dielectric properties of the resin film can be prevented from deteriorating. As a monomer, the liquid crystal polymer filler preferably uses a relative dielectric constant of 2 to 3.5, more preferably 2.7 to 3.2, at 10 GHz or 20 GHz under an environment of 23°C and 50% RH, and a dielectric loss tangent of preferably 0.002 or more, more preferably 0.0015 or less. By setting it within the above range, the dielectric properties of the composition can be prevented from deteriorating when the liquid crystal polymer filler is used.
[0127] As a method for measuring the dielectric properties of liquid crystal polymer fillers, it is possible to measure only the liquid crystal polymer fillers directly as an aggregate or by melt molding. When it is necessary to separate the liquid crystal polymer filler and the components other than the liquid crystal polymer filler from the resin film, as a separation method, the difference in melting point or solubility between the liquid crystal polymer filler and the components other than the liquid crystal polymer filler can be appropriately selected. For example, the resin film can be dissolved in a solvent in which the liquid crystal polymer filler is insoluble and the components other than the liquid crystal polymer filler are soluble, and the unnecessary substances can be separated by filtering and centrifugation. The liquid crystal polymer filler can also be separated by crushing the resin film and treating it at a temperature at which only the liquid crystal polymer filler melts.
[0128] The melting point of a liquid crystal polymer is sometimes referred to as a liquid crystal transition temperature or a liquid crystal transformation temperature, and is preferably 290° C. or higher, more preferably 300° C. or higher, and still more preferably 310° C. or higher. If the melting point is lower than 290° C., the polymer may melt during the manufacturing process of electronic devices, causing changes in properties.
[0129] [Component (B): a matrix polymer that covers and fixes component (A)]
[0130] The matrix polymer of (B) component is a polymer that covers part or all of (A) component and is fixed, which is the matrix resin of the resin film, and is the organic component with the highest content in the composition after removing the liquid crystal polymer filler from the resin film. The matrix polymer of (B) component may be the same as or different from the liquid crystal polymer of the liquid crystal polymer filler constituting the (A) component, but because it is an indefinite shape, it is distinguished from the liquid crystal polymer filler of the (A) component with a specific anisotropic shape. That is, even when (A) component and (B) component both contain liquid crystal polymer, the component with anisotropic shape can also be excluded from the (B) component. As the matrix polymer of (B) component, it is not particularly limited, and in terms of obtaining a resin film with good dielectric properties and low water absorption, for example, preferably fluororesin, polyolefin, polystyrene, polyimide, polyamide, polyether, polyether ketone, polyester, etc. These can also be used in two or more. In addition, in the midway stage of the manufacturing process, the precursor of (B) component can also be compounded with the liquid crystal polymer filler. In order to control the dielectric properties or CTE, bubbles may be mixed into the component (B) to make it porous.
[0131] [Fluororesin]
[0132] Fluororesin is not particularly limited if it is a polymer obtained by polymerizing a fluorine-containing monomer, and for example, polytetrafluoroethylene and a polymer obtained by polymerizing ethylene in which one or more hydrogen groups are replaced by fluorine groups as part of a raw material. For example, preferably a copolymer of tetrafluoroethylene and an olefin, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, tetrafluoroethylene-ethylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, etc. can be cited. Fluororesin with excellent heat resistance, dielectric properties, and low water absorption is preferred.
[0133] Fluororesin films generally have excellent heat resistance, dielectric properties, and low water absorption, and in particular, the dielectric properties show better properties than films containing only liquid crystal polymers. However, since the linear thermal expansion coefficient exceeds 100ppm / K, when used in combination with heterogeneous materials, especially metal materials, warping, peeling, and displacement caused by stress caused by temperature changes are likely to occur. In this embodiment, by compounding the fluororesin with the (A) component, the resin film with the fluororesin as the matrix resin can achieve low CTE while maintaining the above properties.
[0134] [Polyolefin]
[0135] Polyolefins are represented by polyethylene, and are polymers obtained by polymerization of olefins having carbon-carbon double bonds. As monomers, preferably, chain or cyclic olefins such as ethylene, propylene, eicosene, cyclohexene, cyclohexadiene, norbornene, norbornadiene, and dicyclopentadiene can be used, and copolymers of monomers or multiple olefins can be used.
[0136] Polyolefin films generally have excellent dielectric properties and low water absorption, and in particular, dielectric properties show better properties than films containing only liquid crystal polymers. However, they have a high linear thermal expansion coefficient, and when used in combination with heterogeneous materials, especially metal materials, they are prone to warping, peeling, and displacement caused by stress caused by temperature changes. By compounding with liquid crystal polymer fillers, low CTE can be achieved while maintaining the above properties.
[0137] [Polystyrene]
[0138] Polystyrene refers to a polymer obtained by addition polymerization of a compound having an aromatic ring and a carbon-carbon double bond directly or indirectly bonded thereto, represented by styrene and divinylbenzene.
[0139] [Polyimide]
[0140] Polyimide is a polymer having an imide group represented by the following general formula (3). Furthermore, in the case of having an amide group or an ether bond, it is sometimes referred to as polyamide-imide or polyether-imide, but in this specification, these are collectively referred to as polyimide. Such polyimide can be produced by existing methods such as a method of polymerizing a maleimide component with a diamine or triamine component, a method of cross-linking bismaleimide with an aromatic cyanate, a method of using a diamine component and an acid dianhydride component in substantially equimolar amounts and polymerizing them in an organic polar solvent. At this time, heating may also be performed. In the case described above, in order to make the viscosity within the desired range, the molar ratio of the acid dianhydride component to the diamine component may also be adjusted, and the range is preferably set to, for example, within the range of a molar ratio of 0.98 to 1.03.
[0141] [Chemistry 4]
[0142]
[0143] In the general formula (3), Ar1 represents a tetravalent group derived from an acid anhydride including a tetracarboxylic dianhydride residue, R2 represents a divalent diamine residue derived from a diamine, and n is an integer of 1 or more.
[0144] As the acid dianhydride, for example, an aromatic tetracarboxylic dianhydride represented by O(OC)2-Ar1-(CO)2O is preferred, and examples thereof include acid dianhydrides that provide the following aromatic acid anhydride residues as Ar1.
[0145] [Chemistry 5]
[0146]
[0147] In particular, it is preferred that the tetracarboxylic anhydride represented by the following general formula (1) and / or general formula (2) is contained in an amount of 50 mol parts or more, more preferably 80 mol parts or more, based on 100 mol parts of all tetracarboxylic anhydride components.
[0148] [Chemistry 6]
[0149]
[0150] In the general formula (1), X represents a single bond or a divalent group selected from the following formula; in the general formula (2), the cyclic part represented by Y represents a cyclic saturated hydrocarbon group selected from a four-membered ring, a five-membered ring, a six-membered ring, a seven-membered ring or an eight-membered ring.
[0151] [Chemistry 7]
[0152] -CO-, -SO2-, -O-,
[0153] -C(CF3)2-,
[0154] -COO- or -COO-Z-OCO-
[0155] In the above formula, Z represents -C6H4-, -(CH2)n- or -CH2-CH(-OC(=O)-CH3)-CH2-, and n represents an integer of 1 to 20.
[0156] As the diamine, for example, a diamine represented by H2N-R2-NH2 is preferred, and examples thereof include diamines that provide the following diamine residues as R2.
[0157] [Chemistry 8]
[0158]
[0159] Among these diamines, there can be exemplified diaminodiphenyl ether (DAPE), 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), p-phenylenediamine (p-PDA), 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,3-bis(3-aminophenoxy)benzene (APB), 1,4-bis(4-aminophenoxy)benzene (1,4 Preferred substances include 2,2-bis(4-aminophenoxy)benzene (TPE-Q), 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), 2,2-bis(trifluoromethyl)benzidine (TFMB), dimer diamines in which both terminal carboxylic acid groups of dimer acid (dimeric fatty acid) are substituted with primary aminomethyl or amino groups, and dimer diamine compositions containing the same as the main components.
[0160] In particular, the dimer diamine composition can not only achieve low dielectric loss tangent but also improve the toughness of the resin film, and therefore preferably contains a structural unit derived from a diamine component of the dimer diamine composition in an amount of 30 mol% or more, preferably 40 mol% or more relative to all diamine components. Here, the dimer diamine composition is a purified product containing the following component (a) as a main component and controlled amounts of components (b) and (c).
[0161] (a) Dimer diamine
[0162] (b) a monoamine compound obtained by substituting the terminal carboxylic acid group of a monobasic acid compound having 10 to 40 carbon atoms with a primary aminomethyl group or an amino group
[0163] (c) Amine compounds obtained by substituting the terminal carboxylic acid group of a polybasic acid compound having a hydrocarbon group in the range of 41 to 80 carbon atoms with a primary aminomethyl group or an amino group (except the dimer diamine).
[0164] The dimer diamine as the component (a) refers to a diamine in which the two terminal carboxylic acid groups (-COOH) of the dimer acid are substituted with a primary aminomethyl group (-CH2-NH2) or an amino group (-NH2), and can be defined as a diamine compound obtained by replacing the terminal carboxylic acid group of a dibasic acid compound in the range of 18 to 54 carbon atoms, preferably in the range of 22 to 44 carbon atoms, with a primary aminomethyl group or an amino group. The dimer diamine composition preferably uses a dimer diamine composition in which the content of the dimer diamine as the component (a) is increased to 96% by weight or more, preferably 97% by weight or more, and more preferably 98% by weight or more by a purification method such as molecular distillation. By setting the content of the dimer diamine as the component (a) to 96% by weight or more, the expansion of the molecular weight distribution of the polyimide can be suppressed. In addition, if technically feasible, it is most preferred that the entire (100% by weight) of the dimer diamine composition contains the dimer diamine as the component (a).
[0165] The dimer diamine composition can utilize commercial products, and is preferably refined for the purpose of reducing the components other than the dimer diamine as the (a) component, for example, it is preferred that the (a) component is 96% by weight or more. As a refining method, there is no particular restriction, but it is preferably an existing method such as distillation or precipitation purification. As a commercial product of the dimer diamine composition, for example, PRIAMINE 1073 (trade name) manufactured by Croda Japan, PRIAMINE 1074 (trade name) manufactured by Croda Japan, PRIAMINE 1075 (trade name) manufactured by Croda Japan, etc. can be cited.
[0166] The synthesized polyamic acid or polyimide is usually advantageously used as a reaction solvent solution, and can be concentrated, diluted or replaced with other organic solvents as needed to form a resin composition. The method for imidizing the polyamic acid is not particularly limited, for example, a heat treatment such as heating in the solvent at a temperature range of 80°C to 400°C for 1 hour to 24 hours can be preferably used.
[0167] In addition, when the polyimide has a ketone group, the ketone group is reacted with an amino group of an amino compound (hereinafter sometimes referred to as "crosslinking forming amino compound") having at least two primary amino groups as functional groups to form a C=N bond, thereby forming a crosslinked structure. By forming a crosslinked structure, the heat resistance of the polyimide can be improved. As a preferred tetracarboxylic anhydride for forming a polyimide having a ketone group, for example, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (3,3',4,4'-Benzophenonetetracarboxylic dianhydride, BTDA) can be listed, and as a diamine compound, for example, 4,4'-bis (3-aminophenoxy) benzophenone (4,4-bis (3-aminophenoxy) benzophenone, BABP), 1,3-bis [4- (3-aminophenoxy) benzoyl] benzene (1,3-bis [4- (3-aminophenoxy) benzoyl] benzene, BABB) and other aromatic diamines can be listed.
[0168] Examples of the crosslinking amino compound include (I) dihydrazide compounds, (II) aromatic diamines, and (III) aliphatic amines. Among these, dihydrazide compounds are preferred because they can achieve both storage stability of the varnish and shortening of the curing time. As the dihydrazide compound, for example, dihydrazide compounds such as oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, diglycolic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, 2,6-naphthoic acid dihydrazide, 4,4-diphenyl dihydrazide, 1,4-naphthoic acid dihydrazide, 2,6-pyridine dihydrazide, and itaconic acid dihydrazide are preferred. The above dihydrazide compounds may be used alone or in combination of two or more.
[0169] In the case of crosslinking the ketone group in the polyimide with the crosslinking amino compound, the crosslinking amino compound is added to the resin solution containing the polyimide, and the ketone group in the polyimide and the primary amino group of the crosslinking amino compound are subjected to a condensation reaction. Through the condensation reaction, the resin solution is cured to become a cured product. In the case, the amount of the crosslinking amino compound added can be 0.004 mol to 1.5 mol, preferably 0.005 mol to 1.2 mol, relative to 1 mol of the ketone group. Regarding the amount of the crosslinking amino compound added such as the primary amino group is less than 0.004 mol relative to 1 mol of the ketone group, the crosslinking using the crosslinking amino compound is insufficient, so there is a tendency that it is difficult to show the heat resistance after curing. If the amount of the crosslinking amino compound added exceeds 1.5 mol, the unreacted crosslinking amino compound acts as a thermoplastic agent, and there is a tendency to reduce the heat resistance as an adhesive layer.
[0170] The conditions for the condensation reaction for crosslinking formation are not particularly limited as long as the ketone group in the polyimide reacts with the primary amino group of the amino compound for crosslinking formation to form an imine bond (C=N bond). Regarding the temperature of the heating condensation, for the reasons of releasing the water generated by the condensation to the outside of the system, or simplifying the condensation step when the heating condensation reaction is carried out after the synthesis of the polyimide, it is preferably in the range of 120°C to 220°C, and more preferably in the range of 140°C to 200°C. The reaction time is preferably about 30 minutes to 24 hours. The end point of the reaction can be measured, for example, by using a Fourier transform infrared spectrophotometer (commercially available product: FT / IR620 manufactured by JASCO Corporation) to measure the infrared absorption spectrum and using 1670cm -1 The decrease or disappearance of the absorption peak derived from the ketone group in the polyimide resin near 1635 cm -1 This can be confirmed by the appearance of an absorption peak derived from an imine group in the vicinity.
[0171] In the above, in order to impart heat resistance to polyimide, an example of a cross-linked polyimide in which a cross-linked structure is formed by the formation of imide bonds is cited for explanation, but the present invention is not limited to this. As a method for curing polyimide, for example, epoxy resin, epoxy resin hardener, maleimide, activated ester resin, resin having a styrene skeleton, and other compounds having unsaturated bonds can also be formulated for curing.
[0172] Polyimide film is generally excellent in heat resistance, and there is also a polyimide film through low linear thermal expansion coefficient. However, because of the polarity of the imide structure, dielectric loss tangent and water absorption are high, and in the design of the resin composition, low linear thermal expansion coefficient, low dielectric loss tangent and low water absorption are a compromise relationship. By compounding with liquid crystal polymer filler, low dielectric loss tangent and low water absorption can be carried out under the state of maintaining the characteristic. And then, expect a further improvement of heat resistance compared with the film that only comprises liquid crystal polymer.
[0173] [Polyamide]
[0174] Polyamide is not particularly limited, and is a polymer having an amide bond (-CO-NH-) in the skeleton. Such polyamide can be produced by existing methods such as the ring-opening reaction of lactam, the polymerization of a diamine component and a dicarboxylic acid derivative, and the polymerization of a carboxylic acid derivative having an amino group. From the viewpoint of heat resistance, polyamides containing an aromatic skeleton (also collectively referred to as aromatic polyamides) are preferred.
[0175] Polyamide generally has excellent heat resistance, and there is also a polyamide film with low linear thermal expansion coefficient. However, because of the polarity of the amide structure, the dielectric loss tangent and water absorption are high. In the design of the resin composition, low dielectric loss tangent and low water absorption can cause the increase of linear thermal expansion coefficient or the reduction of heat resistance. By compounding with liquid crystal polymer filler, low dielectric loss tangent and low water absorption can be carried out under the state of maintaining the characteristics. And then, it is expected to further improve the heat resistance compared with the film that only comprises liquid crystal polymer.
[0176] [Polyether]
[0177] The polyether is not particularly limited, and is a polymer having an ether bond (-O-) in the skeleton. Such a polyether can be produced by existing methods such as free radical polymerization of phenols. From the viewpoint of heat resistance, a polyphenylene ether (also known as polyphenylene ether, polyphenylene oxide) containing an aromatic skeleton is preferred.
[0178] Polyphenylene ether is generally used for improving processability and functionality and alloying with other synthetic resins, and is referred to as modified polyphenylene ether. The excellent heat resistance of modified polyphenylene ether can realize low linear thermal expansion coefficient, low dielectric loss tangent and low water absorption by compounding with liquid crystal polymer filler. And then, it is expected to further improve the heat resistance compared with the film only comprising liquid crystal polymer.
[0179] [Polyetherketone]
[0180] The polyetherketone is not particularly limited, and is a polymer having an ether bond (-O-) and a carbonyl group (-CO-) in the skeleton. Polyetherketone is generally referred to as polyetherketone, polyetheretherketone, polyetherketoneketone, or polyetherketone ester containing an ester bond, etc., according to its bond configuration. From the viewpoint of heat resistance, it is preferably a polymer containing an aromatic skeleton.
[0181] Polyetheretherketone film generally has excellent heat resistance, and there is also a film with low linear thermal expansion coefficient. However, due to having a ketone structure, the dielectric loss tangent is difficult to reduce. By compounding with a liquid crystal polymer filler, low dielectric loss tangent can be carried out while maintaining the characteristics. And then, it is expected that the further improvement of heat resistance compared with the film only comprising liquid crystal polymer.
[0182] [Polyester]
[0183] Polyester is not particularly limited, and is a polymer having an ester bond (-COO-) in the skeleton. Such polyester can be produced by existing methods such as polymerization of diols and dicarboxylic acid derivatives, transesterification of phenol acetate and carboxylic acid. From the viewpoint of heat resistance, polyesters containing aromatic skeletons such as divalent phenols are preferred.
[0184] The polyester as the component (B) preferably has a melting point lower than that of the liquid crystal polymer filler. This allows composite formation while maintaining the liquid crystal polymer filler.
[0185] [Other polymers]
[0186] The dimer diamine composition can not only achieve low dielectric loss tangent but also improve the toughness of the resin film, so as the matrix polymer of the component (B), there can be cited thermoplastic bismaleimide resin, thermoplastic epoxy resin, thermoplastic polyamide resin, etc., which are polymers using diamine components as raw materials or curing agents and contain 30 mol% or more, preferably 40 mol% or more of the dimer diamine composition relative to all diamine components. By mixing the liquid crystal polymer filler of the component (A) into these polymers, it is possible to take into account both excellent dielectric properties and dimensional stability, thereby forming a resin film suitable as a circuit board material.
[0187] [Precursor]
[0188] As the matrix polymer of component (B), the precursor of the polymer exemplified above can be used. A precursor refers to a substance at a stage before a substance is generated. In this specification, the precursor of a resin also includes an oligomer. As a case where a precursor is preferably used, it can be cited that the precursor is soluble in a polymer that is insoluble in a solvent. Specifically, most wholly aromatic polyimides are insoluble in general solvents, but polyamic acid, which is its precursor, is easily soluble in amide solvents. In addition, even in the case where a high molecular weight body of a polyester is insoluble in a solvent, its oligomer can be solvent-soluble. Generally speaking, an oligomer refers to a polymer with a low degree of polymerization. In this specification, it refers to a polymer with a repetition number in the range of 2 to 50 and a molecular weight of less than 5000. When an oligomer has an active point, the degree of polymerization can be increased by reacting by imparting energy such as heating, increasing the concentration of the solution, or adding an activator or a cross-linking agent.
[0189] [Optional Ingredients]
[0190] The resin film may contain, in addition to component (A) and component (B), a pigment, a flame retardant, a heat dissipating agent, etc. as inorganic components within the scope that does not impair the effects of the invention. Examples of inorganic components include amorphous silicon dioxide, crystalline silicon dioxide (e.g., quartz silicon dioxide, white silica), aluminum oxide, magnesium oxide, beryllium oxide, niobium oxide, titanium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, calcium fluoride, magnesium fluoride, potassium fluorosilicate, and metal salts of phosphinate. These may be used alone or in combination of two or more.
[0191] In addition, in component (B), as additives, for example, catalysts, plasticizers, elastomers, coupling agents, hardeners, hardening accelerators and thermal insulation materials may also be included. These additives may be used alone or in combination. Here, there is no particular limitation on the plasticizer, and a plasticizer corresponding to the type of resin may be used. As preferred plasticizers, trimellitic acid esters, phthalates, low molecular weight polyesters, phosphates, hydrogenated styrene-based and / or hydrogenated butadiene-based elastomers, rubber particles, imidazole compounds, acid anhydrides, dicyandiamide, hydrazides, amine adducts, sulfonium salts, formaldehyde, ketimines, tertiary amines, and organic phosphine compounds may be exemplified.
[0192] The content of the additive is not particularly limited and can be appropriately selected according to the resin component used and process conditions. For example, the content of the additive is preferably 110 wt % or less, and more preferably 90 wt % or less, relative to the content of the component (B).
[0193] [Mixing ratio]
[0194] In the resin film, the mixing ratio of component (A) to component (B) can be appropriately set according to their types. The content of component (A) is preferably within the range of 2% by weight or more and 80% by weight or less, more preferably within the range of 5% by weight or more and 60% by weight or less, and most preferably within the range of 10% by weight or more and 50% by weight or less, relative to the total amount of component (A) and component (B). When the content of component (A) is less than 2% by weight, it is difficult to show the effect of the invention. If it exceeds 80% by weight, the liquid crystal polymer filler may be exposed on the film surface, thereby impairing the smoothness.
[0195] The resin film of the present embodiment having the above composition satisfies the following conditions (i), (ii), and (iii).
[0196] [Condition (i): Average linear thermal expansion coefficient (CTE)]
[0197] The resin film preferably has an average linear thermal expansion coefficient of 50 ppm / K or less at 250°C to 100°C, preferably 30 ppm / K or less. If the absolute value of the average linear thermal expansion coefficient is 50 ppm / K or less, the dimensional change rate during heating can be suppressed, thereby preventing the positional deviation of wirings such as wiring boards when they are joined to each other. Furthermore, if the absolute value of the average linear thermal expansion coefficient is 30 ppm / K or less, the wiring can be made more refined. In addition, if the absolute value of the average linear thermal expansion coefficient exceeds 50 ppm / K, stress will be generated at the interface when it is attached or bonded to a dissimilar material such as a metal, and fragility will be easily generated.
[0198] In addition, the average linear thermal expansion coefficient under the condition (i) refers to the linear thermal expansion coefficient in the longitudinal direction (MD direction) of the resin film.
[0199] [Condition (ii): Dielectric loss tangent]
[0200] When the resin film is used as an insulating resin layer of a circuit substrate, for example, in order to reduce the dielectric loss during high-frequency signal transmission, the dielectric loss tangent (Tanδ) at 20GHz when measured by a separated dielectric resonator (SPDR) at 23°C and 50% RH as a whole film is 0.003 or less, preferably 0.002 or less. In order to improve the transmission loss of the circuit substrate, it is particularly important to control the dielectric loss tangent of the insulating resin layer. By making the dielectric loss tangent within the range, the effect of reducing the transmission loss is increased. Therefore, for example, when the resin film is used as an insulating resin layer of a high-frequency circuit substrate, the transmission loss can be reduced efficiently. If the dielectric loss tangent at 20GHz exceeds 0.003, when the resin film is used as an insulating resin layer of a circuit substrate, it is easy to produce undesirable conditions such as increased electrical signal loss on the transmission path of the high-frequency signal. There is no special restriction on the lower limit of the dielectric loss tangent at 20GHz, but it is necessary to consider the physical property control when the resin film is used as an insulating resin layer of a circuit substrate.
[0201] [Condition (iii): Water absorption]
[0202] In order to reduce the influence of moisture when used for circuit substrates such as printed wiring boards, the water absorption of the resin film is preferably less than 0.2% by weight, preferably less than 0.1% by weight. Here, water absorption refers to the water absorption after 24 hours of immersion in pure water at 23°C (the same meaning in this specification). If the water absorption exceeds 0.2% by weight, when used for circuit substrates such as FPC, it is easily affected by humidity and is prone to adverse conditions such as changes in the transmission speed of high-frequency signals. That is, if the water absorption of the resin film exceeds the range, it is easy to absorb water with a high dielectric constant, which will lead to an increase in the dielectric constant and the dielectric loss tangent, and it is easy to produce adverse conditions such as loss of electrical signals on the transmission path of high-frequency signals.
[0203] [effect]
[0204] It is difficult for existing resin films to take into account both conditions (i) and (ii), but the resin film of this embodiment can simultaneously meet conditions (i) and (ii) by setting the X / Y ratio of the liquid crystal polymer filler of component (A) to more than 2.5. The reason has not yet been fully explained. If the X / Y ratio of the liquid crystal polymer filler with a low dielectric loss tangent is more than 2.5, shear force is applied during the manufacturing process of the liquid crystal polymer filler, so the liquid crystal polymer molecular chains will be oriented in the same direction. As a result, it can be inferred that the average linear thermal expansion coefficient (CTE) of the resin film with the liquid crystal polymer filler is greatly reduced. In this way, the average linear thermal expansion coefficient (CTE) of the resin film can be controlled by utilizing the shape anisotropy of the filler, which is an insight first discovered by the present invention.
[0205] [thickness]
[0206] The overall thickness of the resin film is preferably within a range of 15 μm to 250 μm, more preferably within a range of 25 μm to 200 μm. If the thickness of the resin film is less than 15 μm, the surface smoothness of the film may deteriorate, and undesirable conditions such as wrinkles on the metal foil and damage to the resin film may occur during the conveying step when manufacturing the metal-clad laminate. On the contrary, if the thickness of the resin film exceeds 250 μm, there is a tendency to be disadvantageous in terms of reduced bendability of the resin film.
[0207] [Method for producing resin film]
[0208] The method for manufacturing a resin film may include: preparing a first polymer as a liquid crystal polymer and a second polymer that is the same as or different from the first polymer; orienting the molecules of the first polymer; and compounding the first polymer with the second polymer as a filler. Here, the method for compounding the first polymer with the second polymer as a filler can be appropriately selected according to the shape of the liquid crystal polymer filler of component (A) and the combination of component (B), and is therefore not particularly limited. As preferred methods, for example, the following (1) to (3) can be listed:
[0209] (1) A method of applying a mixture of the liquid crystal polymer filler (A) component, the component (B) and a solvent or dispersion medium as required on an arbitrary substrate and drying it to form a film;
[0210] (2) A method in which the liquid crystal polymer filler of component (A) is immersed in a liquid containing component (B) to form a film;
[0211] (3) A method in which the liquid crystal polymer filler (A) component and the component (B) formed into a film are stacked and pressure-bonded.
[0212] Preferred solvents or dispersion media include, for example, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylformamide, N-methylcaprolactam, dimethyl sulfate, cyclohexane, dioxane, tetrahydrofuran, diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme), cresol, water, etc. Two or more of these solvents or dispersion media may be used in combination, and aromatic hydrocarbons such as xylene and toluene may also be used in combination. The content of the solvent or dispersion medium is not particularly limited, but it is preferably adjusted to an amount of about 5% by weight to 70% by weight.
[0213] When a resin solution containing a liquid crystal polymer filler having a major axis length of less than 10 mm is coated on a substrate, shear stress is generated in the resin solution and the major axis direction of the filler is consistent with the flow direction of the resin, so that the film properties may sometimes have in-plane anisotropy. In order to suppress the in-plane anisotropy, a coating method that is not easy to generate shear stress in a specific direction, such as a spray coater or a curtain coater, can be used. In addition, a method of disturbing the filler in the same direction by using the effect of an electromagnetic field or the like after coating or by extending the obtained film in a specific direction can also be used. Furthermore, films with in-plane anisotropy can also be stacked at specific angles.
[0214] In the present embodiment, a resin composition containing the component (A) and the component (B) is also provided. The composition, blending ratio, etc. of the component (A) and the component (B) in the resin composition of the present embodiment are as described for the resin film. In addition, the resin composition may also contain any of the exemplified components, solvents, or dispersion media as needed.
[0215] {Second Embodiment}
[0216] [Resin composition]
[0217] The resin composition of the present embodiment contains the following components (A) to (C):
[0218] (A) fibrous liquid crystal polymer filler,
[0219] (B) Thermoplastic resin and / or thermosetting resin as matrix polymer
[0220] and
[0221] (C) A particulate metal oxide filler and / or a particulate thermoplastic resin filler.
[0222] [Component (A): Fibrous liquid crystal polymer filler]
[0223] The fibrous liquid crystal polymer filler of component (A) is a fibrous filler with shape anisotropy. Since the average coefficient of thermal expansion (hereinafter sometimes simply referred to as "CTE") of the filler in the long axis direction is low, it contributes to the low CTE of the resin film. In addition, since the fibrous liquid crystal polymer filler has flexibility, it is effective in maintaining the flexibility of the resin film. In the present embodiment, "fibrous" means that the ratio L / D of the average length L of the long axis of the filler to the average diameter D of the short axis orthogonal to the long axis is 2.5 or more. The L / D of the fibrous liquid crystal polymer filler is preferably 4.5 or more, more preferably 15.0 or more, and further preferably 30.0 or more. When L / D is less than 2.5, the fibrous liquid crystal polymer filler is easily disordered in the resin film, thereby reducing the improvement effect of CTE. In addition, the fibrous liquid crystal polymer filler is easily agglomerated with each other.
[0224] The average length L of the major axis of the fibrous liquid crystal polymer filler can be appropriately selected according to the composite method of the fibrous liquid crystal polymer filler and the (B) component. If the dispersibility of the fibrous liquid crystal polymer filler when dispersed in the (B) component is taken into account, it is preferably in the range of 0.1mm to 5mm, and more preferably in the range of 0.2mm to 1mm. When the average length L of the major axis is less than 0.1mm, when the resin composition is cast to form a resin film, the proportion of the fibrous liquid crystal polymer filler oriented in the thickness direction of the film becomes more, resulting in the effect of reducing CTE. On the other hand, if the average length L of the major axis exceeds 5mm, the fibrous liquid crystal polymer filler is entangled with each other, and it is difficult to cast the resin composition to form a resin film. If the average length L of the major axis is within the range, the handleability will not be impaired. In addition, the surface smoothness when forming the resin film will not deteriorate, and a resin film with good appearance can be obtained.
[0225] The average diameter D of the minor axis of the fibrous liquid crystal polymer filler is preferably within a range of 5 μm to 50 μm, more preferably within a range of 10 μm to 30 μm. If the average diameter D of the minor axis is within the above range, the surface smoothness of the resin film will not deteriorate when it is formed, and a resin film with good appearance can be obtained.
[0226] As the liquid crystal polymer constituting the fibrous liquid crystal polymer filler, the same polymer as that in the first embodiment can be used. That is, the structure, structural unit, manufacturing method, surface modification treatment, dielectric properties and their measurement methods, melting point, etc. of the liquid crystal polymer constituting the liquid crystal polymer filler are the same as those in the first embodiment.
[0227] The cross-sectional shape of the fibrous liquid crystal polymer filler is not limited to a circle, and may also be a star shape, a flower shape, a cross shape, or a hollow shape. By changing the cross-sectional shape of the fibrous liquid crystal polymer filler, the surface area of the fibrous liquid crystal polymer filler can be adjusted to control the adhesion with the (B) component or the viscosity of the resin solution.
[0228] [Component (B): Thermoplastic resin and / or thermosetting resin as matrix polymer]
[0229] (B) component is a component that becomes a matrix resin when forming a resin film. As thermoplastic resins that can be used as (B) components, for example, thermoplastic polyimide, thermoplastic bismaleimide resin, thermoplastic epoxy resin, thermoplastic polyamide, liquid crystal polymer, fluororesin, polyolefin, polystyrene, polyether, polyether ketone, polyester, etc. can be cited. In addition, as thermosetting resins that can be used as (B) components, for example, non-thermoplastic polyimide, thermosetting epoxy resin, thermosetting polyphenylene ether, phenol resin, etc. can be cited. The thermoplastic resin and thermosetting resin can be used in combination of two or more. In addition, in this specification, "thermoplastic resin" generally refers to a resin that softens by heating, hardens by cooling, and can repeatedly perform the operation and can clearly confirm the glass transition temperature (Tg), and "non-thermoplastic resin" generally refers to a resin that does not soften even if heated. The material of the component (B) may be the same as or different from the fibrous liquid crystal polymer filler of the component (A) or the particulate thermoplastic resin filler of the component (C), but the component (B) is indefinite in shape and is distinguished from the fibrous liquid crystal polymer filler of the component (A) or the particulate thermoplastic resin filler of the component (C). That is, even when the materials of the components (A), (B) and (C) all include liquid crystal polymers, the component having a fibrous or particulate shape may be excluded from the component (B).
[0230] As component (B), the precursor of the polymer exemplified above can be used. A precursor refers to a substance at a stage before a substance is generated, and in this specification, a precursor of a resin also includes an oligomer. For example, in the case of polyimide, polyamic acid is equivalent to a precursor. As a case where a precursor is preferably used, it can be cited that in a polymer that is insoluble in a solvent, its precursor is still soluble, etc. Specifically, most wholly aromatic polyimides are insoluble in general solvents, but polyamic acid as its precursor is easily soluble in amide solvents. In addition, even in the case where a high molecular weight body of a polyester is insoluble in a solvent, its oligomer can be solvent-soluble. Generally speaking, an oligomer refers to a polymer with a low degree of polymerization, and in this specification, it refers to a polymer with a repetition number in the range of 2 to 50 and a molecular weight of less than 5000. In the case of an oligomer having an active point, the degree of polymerization can be increased by reacting by imparting energy such as heating, increasing the concentration of the solution, or adding an activator or a cross-linking agent.
[0231] Among the resins that can be used as the component (B), particularly preferred resins are polyimide (thermoplastic or non-thermoplastic), liquid crystal polymer, and fluororesin. For these, the resins described in the first embodiment can be used.
[0232] Polyimide films generally have excellent heat resistance, and there are also polyimide films with low CTE. However, due to the polarity of the imide structure, the dielectric loss tangent and water absorption are high. In the design of the resin composition, low CTE and low dielectric loss tangent are a compromise relationship. In the present invention, by compounding with (A) component and (C) component, the resin film with polyimide as the matrix resin can achieve low dielectric loss tangent while maintaining the above characteristics.
[0233] In addition, fluororesin films generally have excellent heat resistance, dielectric properties, and low water absorption, and in particular, the dielectric properties show better properties than films containing only liquid crystal polymers. However, fluororesin films generally have a CTE of more than 100 ppm / K, so when used in combination with heterogeneous materials, especially metal materials, warping, peeling, and displacement caused by stress caused by temperature changes are likely to occur. In the present invention, by compounding fluororesin with component (A) and component (C), the resin film with fluororesin as the matrix resin can achieve low CTE while maintaining the above properties.
[0234] In addition, liquid crystal polymer films generally have excellent dielectric properties, and in order to reduce the CTE difference between the MD direction and the TD direction, a special production method such as an expansion method is required. In the present invention, by compounding the liquid crystal polymer with the (A) component and the (C) component, the CTE difference between the MD direction and the TD direction of the resin film using the liquid crystal polymer as the matrix resin can be alleviated by a simple method without using a special production method, and the dielectric properties can be further improved, thereby achieving a low dielectric loss tangent.
[0235] [Component (C): particulate metal oxide filler and / or particulate thermoplastic resin filler]
[0236] Particulate metal oxide fillers:
[0237] (C) The particulate metal oxide filler of the component refers to a filler with a metal oxide as the main component and in a particle shape. The so-called "particle-like" means that when the average length of the major axis is set to X and the average length of the shortest minor axis in the axis orthogonal to the axis is set to Y, X / Y is less than 2.5, preferably less than 2, more preferably less than 1.5, for example, it can be plate-like, spherical, polyhedral, etc. In addition, the so-called "plate-like" is used in the sense of including, for example, flat, flat, flake, scaly, etc. The thickness of the particulate metal oxide filler refers to a thickness that is sufficiently smaller than the major or minor diameter of the plane part, preferably a thickness of less than 1 / 2. By allocating the particulate metal oxide filler, the CTE and the dielectric loss tangent when forming the resin film can be reduced. In addition, the particulate metal oxide filler does not undergo thermal decomposition at normal combustion temperatures, so it can be added to achieve an improvement in flame retardancy.
[0238] As a particulate metal oxide filler, a spherical filler is most preferably used. Spherical refers to particles whose shape is close to a spherical shape and whose average major diameter to average minor diameter ratio is 1 or close to 1. In addition, with respect to the particulate metal oxide filler, more than 90% by weight of the particles preferably have a circularity of 0.7 or more, and more preferably 0.9 or more. The circularity of the particulate metal oxide filler can be obtained by image analysis, assuming a circle with the same projected area as the photographed particles, and by the ratio of the circumference of the circle to the circumference of the particles. If the circularity is less than 0.7, the surface area increases, which sometimes has an adverse effect on the dielectric properties, and then the increase in viscosity when it is deployed in the resin solution becomes larger, which is difficult to handle. In addition, it is preferably a value that substantially corresponds to the value of the circularity in the sphericity obtained three-dimensionally.
[0239] The particulate metal oxide filler preferably contains 50% by weight or more of the metal oxide, more preferably contains 70% by weight or more. As the metal oxide constituting the particulate metal oxide filler, for example, amorphous silicon dioxide, crystalline silicon dioxide, aluminum oxide, magnesium oxide, beryllium oxide, niobium oxide, titanium oxide, etc. can be cited. Among these, from the perspective of realizing the low dielectric loss tangent when forming the resin film, as described later, the most preferred is crystalline silicon dioxide particles having a white silica crystal phase or a quartz crystal phase.
[0240] Among particulate metal oxide fillers, silica particles having a white silica crystal phase have extremely excellent dielectric properties compared to general silica particles (for example, silica particles containing more than 90 weight percent of a white silica crystal phase have a dielectric loss tangent of approximately 0.0001 at 20 GHz on a monomer basis), which can greatly contribute to lowering the dielectric loss tangent of the resin film.
[0241] Therefore, from the perspective of realizing the low dielectric loss tangent when forming a resin film, as a whole silica particle, preferably, the total area of the peaks of the white silica crystal phase and the quartz crystal phase in the range of 2θ=10°~90° of the X-ray diffraction analysis spectrum using CuKα rays is 20% by weight or more of the silica particles, more preferably 40% by weight or more of the silica particles, and ideally 80% by weight or more of the silica particles. By increasing the proportion of the white silica crystal phase and / or the quartz crystal phase of the whole silica particles, further low dielectric loss tangent of the resin film can be achieved. If the area ratio of the peaks of the white silica crystal phase and the quartz crystal phase in the whole silica particles is less than 20% by weight, the effect of improving the dielectric properties is unclear. In addition, in the case where the peak of the object in the X-ray diffraction analysis spectrum is difficult to separate from the broad peak of the amorphous or overlaps with other crystalline phase peaks, various existing analytical methods, such as the internal standard method or the PONKCS method, can be used.
[0242] The particulate metal oxide filler can be appropriately selected from commercial products. For example, spherical white silica powder (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: CR10-20), spherical amorphous silica powder (manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: SC70-2) and the like can be preferably used. Furthermore, particles of two or more different metal oxides can also be used as the particulate metal oxide filler.
[0243] Particle-shaped thermoplastic resin filler:
[0244] (C) The particle-like thermoplastic resin filler of component refers to a filler with thermoplastic resin as main component and in particle shape. In addition, so-called "particle-like" refers to the average length of the major axis as X, when the average length of the shortest minor axis in the axis orthogonal to the axis is set to Y, X / Y is less than 2.5, preferably less than 2, more preferably less than 1.5, for example, can be plate-like, spherical, polyhedral, etc. In addition, so-called "plate-like" is used with the meaning of including, for example, flat, flat, flake, flaky, etc., and the thickness of the particle-like thermoplastic resin filler refers to a thickness sufficiently smaller than the major or minor diameter of the plane part, preferably a thickness of less than 1 / 2. By allocating the particle-like thermoplastic resin filler, the CTE and dielectric loss tangent when forming the resin film can be reduced.
[0245] As the particulate thermoplastic resin filler, a spherical filler is most preferably used. The spherical filler refers to particles that are close to a spherical shape and have a ratio of an average major axis to an average minor axis of 1 or close to 1.
[0246] Regarding the resin type constituting the particle-shaped thermoplastic resin filler, if it is a resin showing thermoplasticity, it is not particularly limited, and preferably uses, for example, thermoplastic polyimide, liquid crystal polymer, fluororesin, polyolefin, etc. In the present embodiment, when (A) component, (B) component and (C) component are all resin materials, a resin film without inorganic filler can be formed. In the case described, when forming a resin film, the drawbacks of film embrittlement or surface smoothness damage due to inorganic filler can be avoided. In addition, for example, when laser processing is performed in the manufacturing process of a printed wiring board, the precision reduction caused by the inorganic filler can be avoided, so good laser processing can be ensured. In addition, particles of two or more different resin types can also be deployed.
[0247] Among the resin types, liquid crystal polymers in particular have a large effect of reducing dielectric loss tangent when forming resin films, and are a material common to the fibrous liquid crystal polymer filler of component (A), so that the physical property control of resin composition and resin film becomes easy, and are the most preferred resins. In addition, as liquid crystal polymers, polymers with the same structure as component (A) can be preferably used, and as thermoplastic polyimide and fluororesin, polymers with the same structure as component (B) can be preferably used.
[0248] The particulate thermoplastic resin filler can be appropriately selected from commercial products for use. For example, it is preferable to use a material obtained by processing commercially available molded products such as UENO LCP (registered trademark) manufactured by Ueno Pharmaceutical, VECTRA / ZENITE (registered trademark) manufactured by Celanese Japan, Laperos (registered trademark) manufactured by Polyplastics, Siveras (registered trademark) manufactured by Toray, Xydar (registered trademark) manufactured by ENEOS, Teflon (registered trademark) manufactured by Mitsui Chemours Fluoroproducts, Fluon (registered trademark) manufactured by AGC, and ZEONEX (registered trademark) manufactured by ZEON into powder. Furthermore, as the particulate thermoplastic resin filler, particles of two or more different thermoplastic resins may be used in combination.
[0249] Furthermore, as the component (C), a particulate metal oxide filler and a particulate thermoplastic resin filler may be used in combination.
[0250] Volume average particle size D of the particulate metal oxide filler and the particulate thermoplastic resin filler 50It is preferably in the range of 1 μm to 100 μm, and more preferably in the range of 2 μm to 50 μm. 50 " is the value at which the cumulative value in the frequency distribution curve obtained by volume-based particle size distribution measurement using the laser diffraction scattering method is 50%. If the volume average particle size D 50 If the volume average particle size is less than 1 μm, the specific surface area of the particulate metal oxide filler increases, and the adsorbed water or polar groups on the particle surface may affect the dielectric properties. 50 If the volume average particle size D of the particulate metal oxide filler exceeds 100 μm, the particulate metal oxide filler may appear as unevenness on the surface of the resin film, and the smoothness of the film surface may be deteriorated. 50 In the range of 1 μm to 100 μm, it becomes the size of the same degree as the average diameter D of the minor axis of the fibrous liquid crystal polymer filler of (A) component, so it will not affect the smoothness of the film surface, and the particle-shaped metal oxide filler can effectively hinder the orientation and arrangement of the fibrous liquid crystal polymer filler. In addition, the amount of adsorbed water or surface functional groups can be reduced by appropriate particle diameter, so that the dielectric properties can be effectively improved. Therefore, the surface smoothness when the resin film is formed by the resin composition will not be deteriorated, and a resin film with a low dielectric loss tangent having a good appearance and a relaxed anisotropy of CTE can be obtained.
[0251] In addition, the average diameter D of the minor axis of the fibrous liquid crystal polymer filler of the component (A) and the volume average particle diameter D of the particulate metal oxide filler and the particulate thermoplastic resin filler of the component (C) are 50 From the perspective of effectively hindering the orientation and arrangement of the fibrous liquid crystal polymer filler and relaxing the anisotropy of CTE in the resin film, the ratio [D / D 50 ] is preferably in the range of 1 to 50, more preferably in the range of 2 to 30. 50 ] is in the range of 1 to 50, the particulate metal oxide filler strongly hinders the orientation and arrangement of the fibrous liquid crystal polymer filler, and the CTE difference between the MD direction and the TD direction when the resin film is formed can be reduced.
[0252] Furthermore, the average length L of the major axis of the fibrous liquid crystal polymer filler of the component (A) and the volume average particle size D of the particulate metal oxide filler and the particulate thermoplastic resin filler of the component (C) are 50 In terms of effectively hindering the orientation and arrangement of the fibrous liquid crystal polymer filler and relaxing the anisotropy of CTE in the resin film, the ratio [L / D 50 ] is preferably in the range of 10 to 1000, more preferably in the range of 20 to 500. 50] is in the range of 10 to 1000, the particulate metal oxide filler strongly inhibits the orientation and arrangement of the fibrous liquid crystal polymer, and the CTE difference between the MD direction and the TD direction when the resin film is formed can be reduced.
[0253] [Optional Ingredients]
[0254] The resin composition of the present embodiment may contain any component other than components (A) to (C) within the scope that does not impair the effects of the invention. Examples of the optional component include solvents such as organic solvents, organic fillers or inorganic fillers other than components (A) and (C), catalysts, plasticizers, elastomers, coupling agents, hardeners, pigments, flame retardants, heat dissipating agents, and the like. As an organic solvent, for example, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylformamide, N-methylcaprolactam, dimethyl sulfate, cyclohexane, dioxane, tetrahydrofuran, diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme), cresol, etc. can be listed. These solvents can also be used in combination of two or more, and aromatic hydrocarbons such as xylene and toluene can also be used in combination. There is no particular restriction on the content of the organic solvent, and it is preferably used in an amount adjusted to a concentration of component (B) of about 5% by weight to 50% by weight. As organic fillers other than component (A) and component (C), for example, elastomer particles, rubber particles, etc. can be cited. As inorganic fillers other than component (C), for example, nitrides such as boron nitride, aluminum nitride, and silicon nitride, fluorides such as aluminum fluoride, calcium fluoride, magnesium fluoride, and potassium fluorosilicate, metal salts such as phosphinate metal salts, etc. can be cited. These can be used alone or in combination of two or more.
[0255] [Mixing ratio]
[0256] In the resin composition, the blending ratio of each component can be appropriately set according to their types, relative to the content of the solid component (referring to the remainder after removing the solvent) in the resin composition, preferably the total content of the filler of (A) component and (C) component is in the range of 10 volume % to 90 volume %, the content of (B) component is in the range of 10 volume % to 90 volume %, more preferably the total content of the filler of (A) component and (C) component is in the range of 20 volume % to 70 volume %, and the content of (B) component is in the range of 30 volume % to 90 volume %. When the total content of the filler of (A) component and (C) component is less than 10 volume %, it is difficult to show the effect of improving dielectric properties and dimensional stability. If it exceeds 90 volume %, the filler is exposed on the film surface, and sometimes the smoothness is impaired.
[0257] The content of the fibrous liquid crystal polymer filler of component (A) is preferably in the range of 5% to 60% by volume, more preferably in the range of 10% to 50% by volume, relative to the content of the solid component in the resin composition. When the content of component (A) is less than 5% by volume, it is difficult to show the effect of improving the dielectric properties. If it exceeds 60% by volume, the fibrous liquid crystal polymer fillers are entangled with each other and easily form lumps, which reduces the handleability or impairs the surface smoothness.
[0258] The content of the particulate metal oxide filler and the particulate thermoplastic resin filler of the component (C) is preferably in the range of 20 volume % to 80 volume %, more preferably in the range of 30 volume % to 70 volume % relative to the content of the solid component in the resin composition. When the content of the component (C) is less than 20 volume %, it is difficult to fully show the effect of improving the dielectric properties and the effect of hindering the orientation of the fibrous liquid crystal polymer filler of the component (A). If it exceeds 80 volume %, the resin film is easily brittle and the surface smoothness is impaired.
[0259] In addition, the ratio of the content of the component (A) to the total content of the component (C) [component (A) / component (C)] is preferably in the range of 0.1 to 10 on a volume basis. When the ratio [component (A) / component (C)] is in the range of 0.1 to 10, the orientation and arrangement of the fibrous liquid crystal polymer filler of the component (A) can be effectively hindered by the particulate metal oxide filler and / or particulate thermoplastic resin filler of the component (C), and the CTE difference between the MD direction and the TD direction when forming a resin film can be reduced.
[0260] [Method for producing resin composition]
[0261] The method for manufacturing the resin composition of the present embodiment can be appropriately selected according to the types and combinations of components (A) to (C), and is therefore not particularly limited. As a preferred method, it is preferred that the granular metal oxide filler and / or granular thermoplastic resin filler of component (C) be first added to the resin solution formed by dissolving component (B) in an organic solvent, and after uniform mixing, the fibrous liquid crystal polymer filler of component (A) be added and uniformly mixed. If the order of adding component (C) and component (A) is reversed, and component (A) is added before component (C) to the resin solution formed by dissolving component (B) in an organic solvent, the fibrous liquid crystal polymer fillers will be entangled or agglomerated with each other, making it difficult to form a uniform resin composition.
[0262] [Resin film]
[0263] In the present embodiment, a resin film containing the components (A) to (C) is also provided. The resin film of the present embodiment is a resin film having a single or multiple resin layers, and it is sufficient as long as at least one layer of the resin layer is a filler-containing resin layer formed using the resin composition. Among them, the filler-containing resin layer is preferably the main layer of the resin film. Here, the "main layer" refers to a layer having a thickness exceeding 50% relative to the overall thickness of the resin film. Therefore, it is more preferred that the resin film as a whole includes a filler-containing resin layer. In addition, the resin film can, for example, be used as an adhesive layer to constitute a part of the insulating resin layer, and similarly to the first embodiment, can be used as a film, for example, as a bonding sheet.
[0264] In addition, the relative dielectric constant of the filler-containing resin layer at 10 GHz measured by a separated dielectric resonator (SPDR) after humidity adjustment for 24 hours under constant temperature and humidity conditions of 23°C and 50% RH is preferably 3 or less, and the dielectric loss tangent is preferably 0.003 or less. In order to improve the transmission loss of the circuit substrate, it is particularly important to control the dielectric loss tangent of the insulating resin layer. By making the dielectric loss tangent below the value, the effect of reducing the transmission loss is increased. Therefore, for example, when the resin film is used as the insulating resin layer of the high-frequency circuit substrate, the transmission loss can be efficiently reduced. If the dielectric loss tangent at 10 GHz exceeds 0.003, when the resin film is used as the insulating resin layer of the circuit substrate, it is easy to produce undesirable conditions such as increased electrical signal loss on the transmission path of the high-frequency signal.
[0265] In addition, the absolute value of CTE of the filler-containing resin layer in the MD direction at 10° C. to 20° C. is preferably 50 ppm / K or less, and the absolute value of CTE in the TD direction is preferably 100 ppm / K or less. By making the absolute values of CTE in the MD direction and the TD direction less than the above values, the dimensional change before and after heating in the film surface can be suppressed, so that warping can be suppressed, and positional deviation when the wiring of the printed wiring board is joined to each other can be prevented.
[0266] [thickness]
[0267] The overall thickness of the resin film is preferably within a range of 15 μm to 250 μm, and more preferably within a range of 25 μm to 200 μm. If the thickness of the resin film is less than 15 μm, the surface smoothness of the film may deteriorate, and undesirable conditions such as wrinkles on the metal foil and damage to the resin film may occur during the conveying step when manufacturing the metal-clad laminate. On the contrary, if the thickness of the resin film exceeds 250 μm, there is a tendency to be disadvantageous in terms of reduced bendability of the resin film.
[0268] [Method for producing resin film]
[0269] The method for producing the resin film can be appropriately selected according to the types and combinations of components (A) to (C), and is therefore not particularly limited. A preferred method is a casting method in which a resin composition containing components (A) to (C) and an organic solvent is applied to an arbitrary substrate and dried to form a film.
[0270] [effect]
[0271] In the present embodiment, the resin composition contains component (C) while containing component (A) and component (B), thereby relieving the anisotropy of CTE when forming a resin film. The reason is that when the resin composition is cast to form a film, the particulate metal oxide filler and / or particulate thermoplastic resin filler of component (C) moderately hinder the fibrous liquid crystal polymer filler of component (A) from being arranged in the MD direction, thereby relieving the anisotropy of the resin layer containing the filler. As a result, the dimensional change after heating can be suppressed, so by using the resin film of the present embodiment, a more miniaturized and highly refined printed wiring board can be manufactured.
[0272] {Metal-clad laminate}
[0273] The metal-clad laminate of the present embodiment is a metal-clad laminate including an insulating resin layer and a metal layer laminated on at least one side of the insulating resin layer, and at least one layer of the insulating resin layer includes the resin film (preferably the resin film of the first embodiment or the second embodiment). The metal-clad laminate may be a single-sided metal-clad laminate having a metal layer only on one side of the insulating resin layer, or may be a double-sided metal-clad laminate having metal layers on both sides of the insulating resin layer.
[0274] [Insulating resin layer]
[0275] The insulating resin layer includes a single layer or multiple layers, and contains a layer including the resin film. For example, the resin film may also form a non-thermoplastic layer as the main layer of the insulating resin layer for ensuring mechanical properties or thermal properties. In addition, the resin film may also form a thermoplastic resin layer as an adhesive layer that bears the bonding strength with a metal layer such as a copper foil. In addition, the "main layer" refers to a layer that accounts for more than 50% of the total thickness of the insulating resin layer. In addition, the metal-clad laminate of this embodiment does not exclude the use of an adhesive for bonding the resin film to the metal foil. Among them, when an adhesive layer is interposed in a two-sided metal-clad laminate having a metal layer on both sides of the insulating resin layer, in order not to damage the dielectric properties, the thickness of the adhesive layer is preferably set to less than 30% of the thickness of the entire insulating resin layer, and more preferably set to less than 20%. In addition, when an adhesive layer is interposed in a single-sided metal-clad laminate having a metal layer only on one side of the insulating resin layer, in order not to damage the dielectric properties, the thickness of the adhesive layer is preferably set to less than 15% of the thickness of the entire insulating resin layer, and more preferably set to less than 10%. In addition, since the adhesive layer constitutes a part of the insulating resin layer, it is preferably a layer containing the (B) component.
[0276] The thickness of the insulating resin layer is preferably within a range of 35 μm to 200 μm, more preferably within a range of 50 μm to 150 μm, in high-frequency circuit applications. If it is within the above range, the flexibility of the metal-clad laminate and the suppression of the transmission loss of high-frequency signals when the circuit substrate is made can be taken into account.
[0277] As a method for manufacturing a metal-clad laminate having a resin film as an insulating resin layer, for example, the following methods can be cited: a method of applying a resin solution containing the (A) component and the (B) component on a metal foil and subjecting it to vacuum and / or heat treatment; or a method of heat-pressing a metal foil onto a resin film directly or via any adhesive; a method of forming a metal layer on a resin film by a method such as metal evaporation, etc. In addition, a double-sided metal-clad laminate can be obtained, for example, by forming a single-sided metal-clad laminate, placing the resin layers facing each other and pressing them together by hot pressing, or by pressing a metal foil onto the resin layer of a single-sided metal-clad laminate, etc.
[0278] [Metal layer]
[0279] There is no particular limitation on the material of the metal layer, and examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese and alloys thereof. Among these, copper, silver or alloys thereof are particularly preferred. In particular, from the viewpoint of electrical conductivity or cost, it is preferred that the metal layer uses a copper-clad laminate (Copper Clad Laminate, CCL) of copper. The metal layer may be a layer comprising a metal foil, or a layer obtained by metal evaporation on a film, a layer obtained by printing slurry, etc. In addition, in terms of being able to directly apply a resin solution containing component (A) and component (B), a metal foil may be used, and a metal plate may be used, preferably a copper foil or a copper plate.
[0280] The thickness of the metal layer is appropriately set according to the purpose of use of the metal-clad laminate, and is therefore not particularly limited. For example, it is preferably in the range of 5 μm to 3 mm, and more preferably in the range of 12 μm to 1 mm. If the thickness of the metal layer is less than 5 μm, it is possible that undesirable conditions such as wrinkles may occur during the transportation of the metal-clad laminate, etc. On the contrary, if the thickness of the metal layer exceeds 3 mm, it will become hard and the processability will deteriorate. Regarding the thickness of the metal layer, generally speaking, a thick metal layer is suitable for uses such as vehicle-mounted circuit substrates, and a thin metal layer is suitable for uses such as LED circuit substrates.
[0281] {Printed wiring board}
[0282] The printed wiring board of this embodiment is formed by using the metal layer of the metal-clad laminate as a conductor to form a circuit. That is, the printed wiring board includes an insulating resin layer including a single layer or multiple layers, and a circuit wiring layer stacked on at least one side of the insulating resin layer, and at least one layer constituting the insulating resin layer includes the resin film (preferably the resin film of the first embodiment or the second embodiment). In particular, if copper is used in the circuit wiring, it is preferred from the perspective of electrical conductivity or cost. If the transmission loss caused by the high-frequency signal is taken into account, the roughness Rz of the copper side at the interface between the copper and the insulating resin layer is preferably less than 1.5μm, and more preferably less than 1μm. Here, high frequency refers to a frequency of, for example, above 10GHz, especially above 20GHz.
[0283] As described above, the resin film and the metal-clad laminated plate have excellent dielectric properties and dimensional stability by containing the liquid crystal polymer filler of the component (A) and the matrix polymer of the component (B), and the particulate metal oxide filler and / or particulate thermoplastic resin filler of the component (C) as required. Therefore, the resin film and the metal-clad laminated plate can be used as a circuit substrate material of FPC etc. in various electronic devices because the loss in high-frequency signal transmission is reduced and dimensional stability can be maintained.
[0284] [Example]
[0285] The following examples are shown to more specifically describe the features of the present invention. However, the scope of the present invention is not limited to the examples. In addition, in the following examples, various measurements and evaluations are performed using the following methods unless otherwise specified.
[0286] [Determination of water absorption]
[0287] Two test pieces of resin film (4 cm in width x 25 cm in length) were prepared and dried at 80°C for 1 hour. Immediately after drying, they were placed in pure water at 23°C and left to stand for 24 hours, and the weight change before and after was determined using the following formula.
[0288] Water absorption (weight %) = [(weight after water absorption - weight after drying) / weight after drying] × 100
[0289] [Determination method of amine value]
[0290] Weigh about 2 g of the dimer diamine composition into a 200 mL to 250 mL Erlenmeyer flask, use phenolphthalein as an indicator, add 0.1 mol / L ethanolic potassium hydroxide solution until the solution turns light pink, and dissolve it in about 100 mL of neutralized butanol. Add 3 to 7 drops of phenolphthalein solution, and titrate with 0.1 mol / L ethanolic potassium hydroxide solution while stirring until the sample solution turns light pink. Add 5 drops of bromophenol blue solution, and titrate with 0.2 mol / L hydrochloric acid / isopropanol solution while stirring until the sample solution turns yellow.
[0291] The amine value is calculated using the following formula (1).
[0292] Amine value = {(V2×C2)-(V1×C1)}×M KOH / m…(1)
[0293] Here, the amine value is a value expressed by mg-KOH / g, M KOH The molecular weight of potassium hydroxide is 56.1. In addition, V and C are the volume and concentration of the solution used in the titration, respectively, and the subscripts 1 and 2 represent 0.1 mol / L ethanolic potassium hydroxide solution and 0.2 mol / L hydrochloric acid / isopropanol solution, respectively. Furthermore, m is the sample weight expressed in grams.
[0294] [GPC and calculation of area percentage of chromatogram]
[0295] Regarding GPC, 100 mg of a solution obtained by pre-treating 20 mg of a dimer diamine composition with 200 μL of acetic anhydride, 200 μL of pyridine and 2 mL of THF (tetrahydrofuran) was diluted with 10 mL of THF (containing 1000 ppm of cyclohexanone) to prepare a sample. The prepared sample was measured using a product name: HLC-8220GPC manufactured by Tosoh Corporation, under the conditions of column: TSK-gel G2000HXL, G1000HXL, flow rate: 1 mL / min, column (oven) temperature: 40°C, and injection volume: 50 μL. In addition, cyclohexanone was treated as a standard substance in order to correct the elution time.
[0296] At this time, the peak top of the main peak of cyclohexanone was adjusted to a retention time of 27 minutes to 31 minutes, and the peak-to-peak time of the main peak of cyclohexanone was adjusted to 2 minutes, and the peak top of the main peak excluding the peak of cyclohexanone was adjusted to a retention time of 18 minutes to 19 minutes, and the peak-to-peak time of the main peak excluding the peak of cyclohexanone was adjusted to a retention time of 4 minutes and 30 seconds from 2 minutes, and the components (a) to (c) were detected;
[0297] (a) The component represented by the main peak;
[0298] (b) The component represented by the GPC peak detected at a later time than the minimum value on the later retention time side of the main peak;
[0299] (c) The component represented by the GPC peak detected at an earlier time, based on the minimum value on the earlier retention time side of the main peak.
[0300] [Measurement of Weight Average Molecular Weight (Mw) of Polyimide]
[0301] The weight average molecular weight was measured by gel permeation chromatography (manufactured by TOSOH Co., Ltd., HLC-8220GPC was used). Polystyrene was used as a standard substance, and tetrahydrofuran was used as a developing solvent.
[0302] [Evaluation of Dielectric Properties]
[0303] <Liquid crystal polymer filler>
[0304] A dimethylacetamide dispersion of a liquid crystal polymer filler adjusted to 30% by weight of solid content was applied to the smooth surface of the copper foil and dried at 120° C. for 10 minutes. Thereafter, the temperature was gradually raised from 200° C. to the melting point of the liquid crystal polymer + 20° C. over 10 minutes, and the copper foil of the obtained laminate was etched and removed, thereby obtaining a film of a liquid crystal polymer.
[0305] Using a vector network analyzer (manufactured by Keysight Technologies, trade name: Vector Network Analyzer E8363C) and a separated dielectric resonator (SPDR resonator), the obtained liquid crystalline polymer film was placed under conditions of temperature: 23°C and humidity: 50% for 24 hours, and then the relative dielectric constant and dielectric loss tangent at a frequency of 20 GHz were measured.
[0306] <Resin film>
[0307] Using a vector network analyzer (manufactured by Keysight Technologies, trade name: Vector Network Analyzer E8363C) and an SPDR resonator, the resin film that was pressed at a temperature of 160°C, a pressure of 3.5 MPa, and a time of 60 minutes was placed at a temperature of 23°C and a humidity of 50% for 24 hours, and then the relative dielectric constant and dielectric loss tangent at a frequency of 20 GHz were measured.
[0308] [CTE measurement method]
[0309] The resin film was cut into a size of 3 mm × 20 mm, and a thermomechanical analyzer (manufactured by Bruker, trade name: 4000SA) was used. A load of 5.0 g was applied in the longitudinal direction in the tensile mode, and the temperature was raised from 30°C to 260°C at a certain heating rate. After being kept at the temperature for 10 minutes, the film was cooled at a rate of 5°C / min to obtain the average thermal expansion coefficient (thermal expansion coefficient) CTE from 250°C to 100°C. Regarding the CTE in the thickness direction (normal direction, ND) of the resin film, the film was laminated to a thickness of 1 mm, a load of 50 g was applied in the compression mode, the film was heated to 150°C at a heating rate of 10°C / min, and then cooled to 50°C at a cooling rate of 5°C / min to obtain the average thermal expansion coefficient from 150°C to 50°C.
[0310] [Determination of melting point]
[0311] The melting point was measured by using a differential scanning calorimeter (DSC, manufactured by SII, trade name: DSC-6200) in an inert gas atmosphere by raising the temperature from room temperature to 450°C at a rate of 1.5°C / min.
[0312] [Method for measuring the average length of the major axis and the average length of the minor axis]
[0313] The fillers were taken out and observed individually using a stereo microscope, and the lengths of the major axes and minor axes of the taken out fillers were measured.
[0314] [Determination of true specific gravity]
[0315] The true specific gravity was measured by a pycnometer method (liquid phase replacement method) using a continuous automatic powder true density measuring device (manufactured by Seishin Enterprise Co., Ltd., trade name: AUTO TRUE DENSERMAT-7000).
[0316] [Determination of peel strength]
[0317] The peel strength was measured by the following method: The copper-clad laminate was cut into test pieces with a width of 3 mm, and the test piece was stretched in a 90° direction at a speed of 50 mm / min using a tensile tester (manufactured by Toyo Seiki Seisaku-sho, trade name: Strograph VE), and the peel strength between the resin layer and the copper foil was measured.
[0318] [Measurement of surface roughness of copper foil]
[0319] The sample was cut into a size of about 10 mm square, fixed on a sample stand with double-sided tape, irradiated with soft X-rays to remove static electricity on the copper foil surface, and then a scanning probe microscope (AFM, manufactured by Bruker AXS, trade name: Dimension Icon SPM) was used to measure the ten-point average roughness Rz (RzJis) of the copper foil surface under the following measurement conditions.
[0320] Measurement mode: tapping mode
[0321] Measurement area: 1μm×1μm
[0322] Scan speed: 1Hz
[0323] Probe: RTESP-300 manufactured by Buruker
[0324] The abbreviations used in Examples and Comparative Examples represent the following compounds.
[0325] PTFE: Polytetrafluoroethylene
[0326] PFA: Tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer
[0327] PS: Polystyrene
[0328] PI: Polyimide
[0329] PEEK: Polyetheretherketone
[0330] BTDA: 3,3',4,4'-Benzophenonetetracarboxylic dianhydride
[0331] BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride
[0332] DDA: A product obtained by distilling and refining PRIAMINE 1075 (trade name: Croda Japan Co., Ltd.) (component a: 99.2%, component b: 0%, component c: 0.8%, amine value: 210 mgKOH / g)
[0333] BAPP: 2,2-bis[4-(4-aminophenoxy)phenyl]propane
[0334] BAFL: 9,9-bis(4-aminophenyl)fluorene
[0335] N-12: Dodecanedioic acid dihydrazide
[0336] NMP: N-methyl-2-pyrrolidone
[0337] DMAc: N,N-dimethylacetamide
[0338] Liquid crystal polymer A-1: Liquid crystal polymer with polyester structure, melting point (Tm): 350°C, true specific gravity: 1.4, relative dielectric constant: 3.1, dielectric loss tangent: 0.0010
[0339] Liquid crystal polymer A-2: Liquid crystal polymer with polyester structure, melting point (Tm): 330°C, true specific gravity: 1.4, relative dielectric constant: 3.4, dielectric loss tangent: 0.0020
[0340] Liquid crystal polymer A-3: Liquid crystal polymer particles with a polyester structure, melting point (Tm): 320°C, true specific gravity: 1.4, relative dielectric constant: 3.4, dielectric loss tangent: 0.0010
[0341] Shape A-1: short fiber, long axis length: 1 mm, short axis length: 28 μm, manufacturing method: melt spinning and cutting
[0342] Shape A-2: short fiber, long axis length: 0.5 mm, short axis length: 28 μm, manufacturing method: melt spinning and then cutting
[0343] Shape A-3: fabric, fabric composition: plain weave, (twisted yarn of 46 bundles of fibers), yarn density (longitudinal): 14 strands / cm, yarn density (horizontal): 14 strands / cm, cut into 10 cm squares, major axis length: 10 cm, minor axis length: 28 μm, unit area weight: 63 g / m 2 , Manufacturing method: melt spinning and then plain weaving
[0344] Shape A-4: Irregular shape, short axis length: 8 μm, long axis length: 14 μm, manufacturing method: pulverization of particles Shape A-5: Plate-shaped, short axis length: 2 μm, long axis length: 20 μm, manufacturing method: pulverization of films
[0345] In the above-mentioned DDA, "%" of component a, component b, and component c refers to the area percentage of the chromatogram in the GPC measurement.
[0346] [Example A-1]
[0347] To NMP 100g dispersed with 40 wt% PTFE particles, add 40g of liquid crystal polymer A-1 of shape A-1 to obtain resin composition dispersion A-1. The obtained resin composition dispersion A-1 is applied to copper foil A-1 (electrolytic copper foil, thickness: 12 μm, Rz: 0.7 μm), dried at 80 ° C for 15 minutes, and single-sided CCL A-1 is obtained. Copper foil A-2 (electrolytic copper foil, thickness: 12 μm) is overlapped on the resin composition layer side of the obtained single-sided CCL A-1, and heated and pressed at 310 ° C and 6 MPa for 10 minutes to obtain two-sided CCL A-1. Resin film A-1 is obtained by etching and removing the copper foil of the obtained two-sided CCL A-1. The obtained resin film A-1 is evaluated, and the results are thickness: 53 μm, CTE: 42ppm / K, dielectric loss tangent: 0.0007, and water absorption: 0.03wt%.
[0348] [Example A-2]
[0349] 20 g of liquid crystal polymer A-1 of shape A-2 was added to 200 g of DMAc dispersed with 30 wt % PFA particles to obtain a resin composition dispersion A-2. The obtained resin composition dispersion A-2 was applied to copper foil A-1, dried at 100 ° C for 15 minutes, and then heat treated in stages for 20 minutes until 330 ° C to obtain a single-sided CCL A-2. The copper foil of the obtained single-sided CCL A-2 was etched away to obtain a resin film A-2. The obtained resin film A-2 was evaluated, and the results were thickness: 50 μm, CTE: 20 ppm / K, dielectric loss tangent: 0.0007, and water absorption: 0.02 wt %.
[0350] [Example A-3]
[0351] The liquid crystal polymer A-2 of shape A-3 fixed on a stainless steel frame was immersed in DMAc dispersed with 30 wt% PFA particles for 10 minutes, and then tilted and left to stand until no dripping occurred. Dry at 100°C for 15 minutes while fixed to the mold, and then heat treated for 20 minutes in stages until 330°C. Remove from the mold to obtain a resin film A-3. The obtained resin film A-3 was evaluated, and the results were thickness: 140μm, CTE: 30ppm / K, dielectric loss tangent: 0.0028, and water absorption: 0.02wt%.
[0352] [Example A-4]
[0353] Copper foil A-1, PFA film (thickness: 75 μm), liquid crystal polymer A-2 of shape A-3, PFA film (thickness: 75 μm) and copper foil A-2 were stacked in sequence, and heated and pressed at 320°C and 7.5 MPa for 20 minutes in a vacuum environment to obtain double-sided CCL A-4. The copper foil of the obtained double-sided CCL A-4 was etched away to obtain resin film A-4. The obtained resin film A-4 was evaluated, and the results were thickness: 200 μm, CTE: 40 ppm / K, dielectric loss tangent: 0.0025, and water absorption: 0.02 wt%.
[0354] The peel strength of the single-sided CCL A-4 obtained by etching the copper foil A-2 on one side of the double-sided CCL A-4 was 1.3 kN / m.
[0355] [Example A-5]
[0356] Resin film A-5 was obtained in the same manner as in Example A-4 except that a PS film (thickness: 75 μm) was used instead of the PFA film of Example A-4 and the temperature was changed from 320° C. to 250° C. The obtained resin film A-5 was evaluated to have a thickness of 185 μm, a CTE of 35 ppm / K, a dielectric loss tangent of 0.0025, and a water absorption rate of 0.10 wt %.
[0357] (Synthesis Example A-1)
[0358] Into a 500 mL separable flask, 33.84 g of BTDA (0.1048 mol) as an acid anhydride, 56.16 g of DDA (0.1051 mol) as a diamine, 126 g of NMP and 84 g of xylene were placed, and the mixture was fully mixed at 40° C. for 1 hour to prepare a polyamic acid solution. The polyamic acid solution was heated to 190° C., heated for 8 hours and stirred to complete imidization, and 64 g of xylene was added for dilution to prepare a polyimide solution A-1 (solid content: 30 wt %, weight average molecular weight: 58,500). The polyimide composition was set to PIA-1.
[0359] (Synthesis Example A-2 to Synthesis Example A-3)
[0360] Polyimide solution A-2 and polyimide solution A-3 were prepared in the same manner as in Synthesis Example A-1 except that the acid anhydride and the diamine were changed as shown in Table 1. The polyimide compositions were referred to as PIA-2 and PIA-3.
[0361] [Table 1]
[0362]
[0363] [Example A-6]
[0364] 30 wt % of liquid crystal polymer A-1 of shape A-1 and 3.5 wt % of N-12 as a crosslinking agent were mixed into the polyimide solution A-1 obtained in Synthesis Example A-1, and xylene was added to dilute and stir to give a solid content of 15 wt %, thereby preparing a polyimide varnish A-1.
[0365] The prepared polyimide varnish A-1 was cast onto an aluminum substrate, dried at 80° C. for 60 minutes, and then peeled off to prepare a resin film A-6 (thickness: 100 μm).
[0366] Various evaluation results of the resin film A-6 are as follows.
[0367] Relative dielectric constant: 2.7, dielectric loss tangent: 0.0015, CTE: 4ppm / K, water absorption: 0.15wt%
[0368] [Example A-7]
[0369] Resin film A-7 (thickness: 100 μm) was prepared in the same manner as in Example A-6 except that polyimide solution A-2 was used instead of polyimide solution A-1 and the amount of liquid crystal polymer A-1 in shape A-1 was changed to 35 wt %.
[0370] Various evaluation results of the resin film A-7 are as follows.
[0371] Relative dielectric constant: 2.7, dielectric loss tangent: 0.0013, CTE: 2ppm / K, water absorption: 0.18wt%
[0372] [Example A-8]
[0373] Resin film A-8 (thickness: 100 μm) was prepared in the same manner as in Example A-6 except that polyimide solution A-3 was used instead of polyimide solution A-1 and the amount of liquid crystal polymer A-1 in shape A-1 was changed to 50 wt %.
[0374] Various evaluation results of resin film A-8 are as follows.
[0375] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0015, CTE: 1ppm / K, water absorption: 0.12wt%
[0376] [Example A-9]
[0377] 3.5 wt % of N-12 was mixed as a crosslinking agent in the polyimide solution A-1 obtained in Synthesis Example A-1, and xylene was added to dilute the mixture to a solid content of 15 wt %, followed by stirring to prepare a polyimide varnish A-1a.
[0378] The prepared polyimide varnish A-1a was applied on one side of a release-treated PET film, dried at 80°C for 15 minutes and at 120°C for 5 minutes, and then peeled off to prepare a polyimide film A-1a (thickness: 25 μm).
[0379] Two polyimide films A-1a were stacked and used with a thickness of 50 μm instead of the PFA film 75 μm of Example A-4, and the heating and pressing conditions were changed to 160° C. and 5 MPa for 60 minutes in a vacuum environment. Double-sided CCL A-9 and resin film A-9 were obtained in the same manner as Example A-4. The obtained resin film A-9 was evaluated, and the results were: thickness: 157 μm, CTE: -20 ppm / K, dielectric loss tangent: 0.0027, and water absorption: 0.15 wt%.
[0380] The peel strength of the single-sided CCL A-9 obtained by etching the copper foil A-2 on one side of the double-sided CCL A-9 was 1.4 kN / m.
[0381] [Example A-10]
[0382] Resin film A-10 was obtained in the same manner as in Example A-4 except that a PEEK film (thickness: 75 μm) was used instead of the PFA film. The obtained resin film A-10 was evaluated to have a thickness of 190 μm, a CTE of 5 ppm / K, a dielectric loss tangent of 0.0025, and a water absorption rate of 0.05 wt%.
[0383] [Example A-11]
[0384] In DMAc dispersed with 30 wt% of polyester microparticles having a skeleton derived from p-hydroxybenzoic acid and hydroxynaphthoic acid, a liquid crystal polymer A-2 of shape A-3 fixed on a stainless steel frame was immersed for 10 minutes, and then tilted and allowed to stand until no dripping occurred. Dry at 100°C for 15 minutes while fixed to the mold, and then heat treated in stages for 20 minutes until 330°C. Remove from the mold to obtain a resin film A-11. The obtained resin film A-11 was evaluated, and the results were thickness: 145μm, CTE: 10ppm / K, dielectric loss tangent: 0.0015, and water absorption: 0.10wt%.
[0385] [Example A-12]
[0386] 30 g of the liquid crystal polymer A-3 of shape A-5 was mixed with 100 g of water in which 30 wt % of polyester microparticles having a skeleton derived from p-hydroxybenzoic acid and hydroxynaphthoic acid and having a melting point of 300° C. were dispersed, and the mixture was cast onto a polyimide film substrate. The mixture was dried at 100° C. for 15 minutes, and then heat-treated at 310° C. for 20 minutes in stages, and then peeled off from the polyimide film substrate to obtain a resin film A-12. The obtained resin film A-12 was evaluated to have a thickness of 85 μm, a CTE of 14 ppm / K, a dielectric loss tangent of 0.0020, and a water absorption rate of 0.11 wt %.
[0387] Furthermore, a liquid crystal polymer A-3 having a shape A-5 was prepared by the following method.
[0388] First, the liquid crystal polymer A-3 was melt-extruded to prepare a sheet with a thickness of 0.4 mm and a square of 10 cm. The CTE in the extrusion direction (MD direction) was -40 ppm / K, the CTE in the thickness direction (ND direction) was 150 ppm / K, and the CTE in the direction perpendicular to the plane formed by the extrusion direction and the thickness direction (TD direction) was 130 ppm / K. Next, the sheet was subdivided using a crusher to obtain a plate-like liquid crystal polymer filler.
[0389] [Example A-13]
[0390] 5 wt % of liquid crystal polymer A-1 of shape A-1 and 3.5 wt % of N-12 as a crosslinking agent were mixed with polyimide solution A-1 obtained in Synthesis Example A-1, and xylene was added to dilute and stir to give a solid content of 30 wt %, thereby preparing polyimide varnish A-13.
[0391] The prepared polyimide varnish A-13 was cast onto copper foil A-1, dried at 80°C for 60 minutes, and then heat treated at 160°C for 1 hour to obtain single-sided CCL A-13. Next, the copper foil A-1 was removed to prepare a resin film A-13 (thickness: 100 μm).
[0392] The various evaluation results of the resin film A-13 and the single-sided CCL A-13 are as follows.
[0393] Relative dielectric constant: 2.1, dielectric loss tangent: 0.0017, CTE: 26ppm / K, water absorption: 0.17wt%, peel strength: 1.1kN / m
[0394] (Comparative Example A-1)
[0395] Resin film A was prepared in the same manner as in Example A-1 except that liquid crystal polymer A-1 of shape A-1 was not added. The obtained resin film A was evaluated to have a thickness of 50 μm, a CTE of 250 ppm / K, a dielectric loss tangent of 0.0003, a relative dielectric constant of 2.1, and a water absorption of 0.01 wt %.
[0396] (Comparative Example A-2)
[0397] Resin film B was prepared in the same manner as in Example A-2 except that liquid crystal polymer A-1 of shape A-2 was not added. The obtained resin film B was evaluated to have a thickness of 50 μm, CTE of 296 ppm / K, dielectric loss tangent of 0.0009, relative dielectric constant of 2.0, and water absorption of 0.01 wt %.
[0398] (Comparative Example A-3)
[0399] Resin film C was prepared in the same manner as in Example A-5 except that liquid crystal polymer A-2 of shape A-3 was not laminated. Evaluation of the obtained resin film C revealed a thickness of 145 μm, CTE of 80 ppm / K, dielectric loss tangent of 0.0005, and water absorption of 0.12 wt %.
[0400] (Comparative Example A-4)
[0401] A resin film D (thickness: 100 μm) was prepared in the same manner as in Example A-6 except that the liquid crystal polymer A-1 of the shape A-1 was not added.
[0402] Various evaluation results of the resin film D are as follows.
[0403] Relative dielectric constant: 2.6, dielectric loss tangent: 0.0017, CTE: 150ppm / K, water absorption: 0.10wt%.
[0404] (Comparative Example A-5)
[0405] A resin film E (thickness: 100 μm) was prepared in the same manner as in Example A-7 except that the liquid crystal polymer A-1 of the shape A-1 was not added.
[0406] Various evaluation results of the resin film E are as follows.
[0407] Relative dielectric constant: 2.6, dielectric loss tangent: 0.0014, CTE: 109ppm / K, water absorption: 0.08wt%
[0408] (Comparative Example A-6)
[0409] A resin film F (thickness: 100 μm) was prepared in the same manner as in Example A-8 except that the liquid crystal polymer A-1 of the shape A-1 was not added.
[0410] Various evaluation results of the resin film F are as follows.
[0411] Relative dielectric constant: 2.7, dielectric loss tangent: 0.0017, CTE: 115ppm / K, water absorption: 0.12wt%
[0412] (Comparative Example A-7)
[0413] Resin film G was prepared in the same manner as in Example A-6 except that liquid crystal polymer A-3 of shape A-4 was used instead of liquid crystal polymer A-1 of shape A-1. The obtained resin film G was evaluated to have a thickness of 56 μm, a CTE of 70 ppm / K, a dielectric loss tangent of 0.0013, a relative dielectric constant of 3.2, and a water absorption of 0.12 wt%.
[0414] (Comparative Example A-8)
[0415] Resin film H was prepared in the same manner as in Example A-10 except that liquid crystal polymer A-2 of shape A-3 was not laminated. Evaluation of the obtained resin film H revealed a thickness of 98 μm, CTE of 40 ppm / K, dielectric loss tangent of 0.0040, relative dielectric constant of 3.1, and water absorption of 0.07 wt %.
[0416] (Comparative Example A-9)
[0417] Resin film I was prepared in the same manner as in Example A-12 except that liquid crystal polymer A-3 of shape A-5 was not added. Evaluation of the obtained resin film I revealed a thickness of 74 μm, a CTE of 90 ppm / K, a dielectric loss tangent of 0.0010, and a water absorption of 0.05 wt %.
[0418] The above results are summarized in Table 2.
[0419] [Table 2]
[0420]
[0421] Table 2 shows that the resin films of Examples A-1 to A-13 in which the liquid crystal polymer filler of the component (A) is compounded with the matrix polymer of the component (B) can achieve both a small linear thermal expansion coefficient and a low dielectric loss tangent, and can ensure dimensional stability while coping with high-frequency signal transmission. In contrast, the results of the resin films of Comparative Examples A-1 to A-6, A-8, and A-9 in which the liquid crystal polymer filler is not mixed are large in linear thermal expansion coefficient or high in dielectric loss tangent, and the result of Comparative Example A-7 in which the shape anisotropy (X / Y) of the liquid crystal polymer filler is less than 2.5 is large in linear thermal expansion coefficient.
[0422] In addition to the above, various measurements and evaluations in the following examples were performed as follows.
[0423] [Evaluation of Dielectric Properties]
[0424] <Silica particles>
[0425] A vector network analyzer (manufactured by Keysight Technologies, trade name: vector network analyzer E8363C) and a relative dielectric constant measuring device manufactured by Kanto Electronics Application Development Co., Ltd. using a resonant cavity perturbation method were used, set to relative dielectric constant measurement mode: TM020, and the relative dielectric constant (ε1) and dielectric loss tangent (Tanδ1) of the silica particles at a frequency of 10 GHz were measured. In addition, the silica particles were in powder form and filled into a sample tube (inner diameter of 1.68 mm, outer diameter of 2.28 mm, height of 8 cm) for measurement.
[0426] <Liquid crystal polymer short fibers>
[0427] A dimethylacetamide dispersion of liquid crystal polymer short fibers adjusted to 10% by weight of solid content was applied to the smooth surface of the copper foil and dried at 120° C. for 20 minutes. Thereafter, a new copper foil was laminated so that its smooth surface was in contact with the coated liquid crystal polymer short fiber layer, and vacuum pressure bonding was performed at the melting point of the liquid crystal polymer + 20° C. for 10 minutes, and the copper foil of the obtained laminate was etched and removed, thereby obtaining a film of a liquid crystal polymer.
[0428] Using a vector network analyzer (manufactured by Keysight Technologies, trade name: Vector Network Analyzer E8363C) and a separated dielectric resonator (SPDR resonator), the obtained liquid crystalline polymer film was placed under temperature: 23°C and humidity: 50% for 24 hours, and then the relative dielectric constant and dielectric loss tangent at a frequency of 10 GHz were measured.
[0429] <Resin film>
[0430] Using a vector network analyzer (manufactured by Keysight Technologies, trade name: Vector Network Analyzer E8363C) and an SPDR resonator, the resin film that was pressed at a temperature of 160°C, a pressure of 3.5 MPa, and a time of 60 minutes was placed at a temperature of 23°C and a humidity of 50% for 24 hours, and then the relative dielectric constant and dielectric loss tangent at a frequency of 10 GHz were measured.
[0431] [CTE measurement method]
[0432] The resin film was cut into a size of 3 mm × 20 mm and a thermal mechanical analyzer (manufactured by Bruker, trade name: 4000SA) was used. A load of 5.0 g was applied in the tensile mode and the temperature was raised from 5°C to 300°C at a certain heating rate. The average thermal expansion coefficient (average linear thermal expansion coefficient: CTE) from 10°C to 20°C was measured and calculated for the MD and TD directions of the film.
[0433] [Method for measuring the average length of the major axis and the average length of the minor axis]
[0434] Ten fibrous liquid crystal polymer fillers were randomly selected and observed independently using a stereo microscope. The lengths of the major axis and the minor axis of each of the selected fillers were measured and the average values were calculated.
[0435] [Measurement of circularity]
[0436] The average circularity of the silica particles was measured by a wet flow particle size and shape analyzer (manufactured by Sysmex Corporation, trade name: FPIA-3000) using dynamic flow particle image analysis.
[0437] [Volume average particle size D 50 Determination of
[0438] The volume average particle size of the silica particles was measured by a laser diffraction-scattering measurement method using water as a dispersion medium and a particle refractive index of 1.54 using a laser diffraction-scattering measurement apparatus (manufactured by Malvern, trade name: Master Sizer 3000).
[0439] [Determination of white silica crystal phase]
[0440] Using an X-ray diffraction measuring device (manufactured by Bruker, trade name: D2PHASER), the total area of all peaks originating from SiO2 was calculated based on all diffraction patterns (peak position, peak width and peak intensity) originating from SiO2 in the range of diffraction angle (Cu, Kα) 2θ = 10° to 90°. Next, the peak position originating from the white silica crystalline phase was determined, the total area of all peaks of the white silica crystalline phase was calculated, and the ratio (weight %) to the total area of all peaks originating from SiO2 was obtained. In addition, the attribution of each peak was referenced to the database of the International Centre for Diffraction Data (ICDD).
[0441] [Evaluation of heat resistance of humidified solder]
[0442] The roughened surface of the copper foil is laminated with the resin side of the prepared copper-clad laminate, and a double-sided copper-clad laminate is prepared by heat pressing. The obtained double-sided copper-clad laminate is cut into 30 mm squares, and the test piece is placed at 23°C and relative humidity: 50% for 72 hours, and then immersed in a solder bath set at 288°C for 10 seconds, and its bonding state is observed to confirm whether there are any undesirable conditions such as foaming, expansion, and peeling. The case where no undesirable condition occurs is set as good, and the case where an undesirable condition occurs is set as unacceptable.
[0443] The abbreviations used in Examples and Comparative Examples represent the following compounds.
[0444] PI: Polyimide
[0445] PMDA: Pyromellitic Dianhydride
[0446] m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl
[0447] LCP: Liquid Crystal Polymer
[0448] LCP B-1: Liquid crystal polymer with polyester structure, melting point (Tm): 350°C, true specific gravity: 1.4, relative dielectric constant: 3.1, dielectric loss tangent: 0.0010
[0449] LCP B-2: Liquid crystal polymer with polyester structure, melting point (Tm): 330°C, true specific gravity: 1.4, relative dielectric constant: 3.4, dielectric loss tangent: 0.0020
[0450] LCP B-3: Liquid crystal polymer with polyester structure, melting point (Tm): 320°C, true specific gravity: 1.4, relative dielectric constant: 3.4, dielectric loss tangent: 0.0008
[0451] Shape B-1: short fiber, average length of long axis: 0.5 mm, average length of short axis: 28 μm, manufacturing method: melt spinning and cutting
[0452] Shape B-2: short fiber, average length of long axis: 3 mm, average length of short axis: 28 μm, manufacturing method: melt spinning and cutting
[0453] Particle B-1: manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: CR10-20 (spherical white silica silicon dioxide powder, circularity: 0.98, white silica crystal phase: 98 wt%, true specific gravity: 2.33, D 50 : 10.8μm, relative dielectric constant at 10GHz: 3.16, dielectric loss tangent at 10GHz: 0.0008)
[0454] Particle B-2: manufactured by Admatech, trade name: SE4050 (spherical amorphous silica powder, spherical shape, true specific gravity: 2.21, D 50 : 1.5μm, relative dielectric constant at 10GHz: 2.92, dielectric loss tangent at 10GHz: 0.0052)
[0455] Particle B-3: manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: SC70-2 (spherical amorphous silica powder, circularity: 0.98, true specific gravity: 2.21, D 50 : 11.7μm, relative dielectric constant at 10GHz: 3.08, dielectric loss tangent at 10GHz: 0.0015)
[0456] (Synthesis Example B-1 to Synthesis Example B-3)
[0457] Polyimide solution B-1, polyimide solution B-2, and polyimide solution B-3 were prepared in the same manner as in Synthesis Example A-1, Synthesis Example A-2, and Synthesis Example A-3, respectively.
[0458] (Synthesis Example B-4)
[0459] 19 g of m-TB (90 mmol) and 230 g of DMAc were added to a 300 ml separable flask and stirred at room temperature under a nitrogen stream. After complete dissolution, 16 g of PMDA (72 mmol) and 5.3 g of BPDA (18 mmol) were added and stirred at room temperature for 18 hours to obtain a polyamic acid solution B-1. The viscosity of the obtained polyamic acid solution B-1 was 22,400 cps. The polyimide obtained after the polyamic acid solution B-1 was hardened was set to PI B-4.
[0460] (Synthesis Example B-5)
[0461] 24 g of BAPP (60 mmol) and 230 g of DMAc were added to a 300 ml separable flask and stirred at room temperature under nitrogen flow. After complete dissolution, 6.5 g of PMDA (30 mmol) and 8.7 g of BPDA (30 mmol) were added and stirred at room temperature for 18 hours to obtain polyamic acid solution B-2. The viscosity of the obtained polyamic acid solution B-2 was 21,074 cps. The polyimide obtained after the polyamic acid solution B-2 was hardened was set to PI B-5.
[0462] [Example B-1]
[0463] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution B-1 obtained in Synthesis Example B-1, 115 g of particles B-1 were added, and after stirring, 11.7 g of LCP B-1 in shape B-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish B-1. Regarding the volume-based content of the total solid content in the polyimide varnish B-1, LCP B-1 was 10%, and particles B-1 was 60%.
[0464] The prepared polyimide varnish B-1 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and then treated at 160°C for 1 hour to prepare a copper-clad laminate B-1. The copper foil was then etched to prepare a resin film B-1 (thickness: 145 μm).
[0465] The various evaluation results of the resin film B-1 and the copper-clad laminate B-1 are as follows.
[0466] Relative dielectric constant: 2.5, dielectric loss tangent: 0.0009, CTE (TD): 58ppm / K, CTE (MD): 17ppm / K, peel strength: 1.3kN / m, humidified solder heat resistance: good
[0467] [Example B-2]
[0468] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution B-1 obtained in Synthesis Example B-1, 19.2 g of particles B-1 were added, and after stirring, 11.7 g of LCP B-1 in shape B-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish B-2. Regarding the volume-based content of the total solid content in the polyimide varnish B-2, LCP B-1 was 20%, and particles B-1 was 20%.
[0469] The prepared polyimide varnish B-2 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and then treated at 160°C for 1 hour to prepare a copper-clad laminate B-2. The copper foil was then etched to prepare a resin film B-2 (thickness: 113 μm).
[0470] Various evaluation results of the resin film B-2 are as follows.
[0471] Relative dielectric constant: 1.9, dielectric loss tangent: 0.0015, CTE (TD): 91ppm / K, CTE (MD): 20ppm / K, humidified solder heat resistance: good
[0472] [Example B-3]
[0473] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution B-1 obtained in Synthesis Example B-1, 57.5 g of particles B-1 were added, and after stirring, 17.5 g of LCP B-1 in shape B-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish B-3. Regarding the volume-based content of the total solid content in the polyimide varnish B-3, LCP B-1 was 20%, and particles B-1 was 40%.
[0474] The prepared polyimide varnish B-3 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and then treated at 160°C for 1 hour to prepare a copper-clad laminate B-3. The copper foil was then etched to prepare a resin film B-3 (thickness: 135 μm).
[0475] Various evaluation results of the resin film B-3 are as follows.
[0476] Relative dielectric constant: 2.0, dielectric loss tangent: 0.0013, CTE (TD): 70ppm / K, CTE (MD): 17ppm / K
[0477] [Example B-4]
[0478] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution B-1 obtained in Synthesis Example B-1, 28.8 g of particles B-1 were added, and after stirring, 35 g of LCP B-1 in shape B-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish B-4. Regarding the volume basis content of the total solid content in the polyimide varnish B-4, LCP B-1 was 40%, and particles B-1 was 20%.
[0479] The prepared polyimide varnish B-4 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and then treated at 160°C for 1 hour to prepare a copper-clad laminate B-4. The copper foil was then etched to prepare a resin film B-4 (thickness: 58 μm).
[0480] The various evaluation results of the resin film B-4 and the copper-clad laminate B-4 are as follows.
[0481] Relative dielectric constant: 1.8, dielectric loss tangent: 0.0009, CTE (TD): 69ppm / K, CTE (MD): 30ppm / K, peel strength: 1.2kN / m, humidified solder heat resistance: good
[0482] [Example B-5]
[0483] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution B-1 obtained in Synthesis Example B-1, 18.3 g of particles B-2 were added, and after stirring, 11.7 g of LCP B-1 in shape B-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish B-5. Regarding the volume basis content of the total solid content in the polyimide varnish B-5, LCP B-1 was 20%, and particles B-2 was 20%.
[0484] The prepared polyimide varnish B-5 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and then treated at 160°C for 1 hour to prepare a copper-clad laminate B-5. The copper foil was then etched to prepare a resin film B-5 (thickness: 158 μm).
[0485] Various evaluation results of the resin film B-5 are as follows.
[0486] Relative dielectric constant: 2.0, dielectric loss tangent: 0.0015, CTE (TD): 87ppm / K, CTE (MD): 15ppm / K, humidified solder heat resistance: good
[0487] [Example B-6]
[0488] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution B-1 obtained in Synthesis Example B-1, 55 g of particles B-2 were added, and after stirring, 17.5 g of LCP B-1 in shape B-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish B-6. Regarding the volume basis content of the total solid content in the polyimide varnish B-6, LCP B-1 was 20%, and particles B-2 was 40%.
[0489] The prepared polyimide varnish B-6 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and then treated at 160°C for 1 hour to prepare a copper-clad laminate B-6. The copper foil was further etched to prepare a resin film B-6 (thickness: 178 μm).
[0490] Various evaluation results of the resin film B-6 and the copper-clad laminate B-6 are as follows.
[0491] Relative dielectric constant: 2.2, dielectric loss tangent: 0.0016, CTE (TD): 57ppm / K, CTE (MD): 15ppm / K, peel strength: 1.1kN / m, humidified solder heat resistance: good
[0492] [Example B-7]
[0493] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution B-1 obtained in Synthesis Example B-1, 33 g of particles B-3 were added, and after stirring, 14 g of LCP B-1 of shape B-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish B-7. Regarding the volume-based content of the total solid content in the polyimide varnish B-7, LCP B-1 was 20%, and particles B-3 was 30%.
[0494] The prepared polyimide varnish B-7 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and then treated at 160°C for 1 hour to prepare a copper-clad laminate B-7. The copper foil was further etched to prepare a resin film B-7 (thickness: 108 μm).
[0495] Various evaluation results of the resin film B-7 are as follows.
[0496] Relative dielectric constant: 1.9, dielectric loss tangent: 0.0016, CTE (TD): 80ppm / K, CTE (MD): 23ppm / K, humidified solder heat resistance: good
[0497] [Example B-8]
[0498] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution B-2 obtained in Synthesis Example B-2, 19.2 g of particles B-1 were added, and after stirring, 11.7 g of LCP B-1 in shape B-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish B-8. Regarding the volume-based content of the total solid content in the polyimide varnish B-8, LCP B-1 was 20%, and particles B-1 was 20%.
[0499] The prepared polyimide varnish B-8 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and then treated at 160°C for 1 hour to prepare a copper-clad laminate B-8. The copper foil was further etched to prepare a resin film B-8 (thickness: 102 μm).
[0500] Various evaluation results of the resin film B-8 are as follows.
[0501] Relative dielectric constant: 1.9, dielectric loss tangent: 0.0011, CTE (TD): 70ppm / K, CTE (MD): 22ppm / K
[0502] [Example B-9]
[0503] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution B-3 obtained in Synthesis Example B-3, 19.2 g of particles B-1 were added, and after stirring, 11.7 g of LCP B-1 in shape B-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish B-9. Regarding the volume-based content of the total solid content in the polyimide varnish B-9, LCP B-1 was 20%, and particles B-1 was 20%.
[0504] The prepared polyimide varnish B-9 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and then treated at 160°C for 1 hour to prepare a copper-clad laminate B-9. The copper foil was further etched to prepare a resin film B-9 (thickness: 97 μm).
[0505] Various evaluation results of the resin film B-9 and the copper-clad laminate B-9 are as follows.
[0506] Relative dielectric constant: 2.0, dielectric loss tangent: 0.0014, CTE (TD): 75ppm / K, CTE (MD): 20ppm / K, peel strength: 1.5kN / m, humidified solder heat resistance: good
[0507] [Example B-10]
[0508] 7 g of particles B-1 were added to 100 g of the polyamic acid solution B-1 obtained in Synthesis Example B-4, and after stirring, 2.1 g of LCP B-1 in shape B-2 was added, and DMAc was added to dilute and stir in a manner such that the total solid content concentration became 20% by weight, thereby preparing polyamic acid varnish B-1. Regarding the volume-based content of the total solid content in the polyamic acid varnish B-1, LCP B-1 was 10%, and particles B-1 was 20%.
[0509] The prepared polyamic acid varnish B-1 was cast onto an electrolytic copper foil (12 μm) and dried at 130° C. for 3 minutes. Thereafter, a stepwise heat treatment was performed from 155° C. to 360° C. for imidization to prepare a copper-clad laminate B-10. Furthermore, the copper foil was etched to prepare a resin film B-10 (thickness: 40 μm).
[0510] Various evaluation results of the resin film B-10 are as follows.
[0511] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0028, CTE (TD): 10ppm / K, CTE (MD): 4ppm / K
[0512] [Example B-11]
[0513] 7 g of particles B-1 were added to 100 g of the polyamic acid solution B-1 obtained in Synthesis Example B-4, and after stirring, 2.1 g of LCP B-2 in shape B-2 was added, and DMAc was added to dilute and stir in a manner such that the total solid content concentration became 20% by weight, thereby preparing polyamic acid varnish B-2. Regarding the volume-based content of the total solid content in the polyamic acid varnish B-2, LCP B-2 was 10%, and particles B-1 was 20%.
[0514] The prepared polyamic acid varnish B-2 was cast onto an electrolytic copper foil (12 μm) and dried at 130° C. for 3 minutes. Thereafter, a stepwise heat treatment was performed from 155° C. to 360° C. for imidization to prepare a copper-clad laminate B-11. Furthermore, the copper foil was etched to prepare a resin film B-11 (thickness: 48 μm).
[0515] Various evaluation results of the resin film B-11 are as follows.
[0516] Relative dielectric constant: 2.9, dielectric loss tangent: 0.0028, CTE (TD): 18ppm / K, CTE (MD): 17ppm / K, humidified solder heat resistance: good
[0517] [Example B-12]
[0518] 6.9 g of particle B-2 was added to 100 g of the polyamic acid solution B-2 obtained in Synthesis Example B-5, and after stirring, 4.2 g of LCP B-1 in shape B-2 was added, and DMAc was added to dilute and stir in such a way that the total solid content concentration became 15% by weight, thereby preparing polyamic acid varnish B-3. Regarding the volume-based content of the total solid content in the polyamic acid varnish B-3, LCP B-1 was 20%, and particle B-2 was 20%.
[0519] The prepared polyamic acid varnish B-3 was cast onto an electrolytic copper foil (12 μm) and dried at 130° C. for 3 minutes. Thereafter, a stepwise heat treatment was performed from 155° C. to 360° C. for imidization to prepare a copper-clad laminate B-12. Furthermore, the copper foil was etched to prepare a resin film B-12 (thickness: 55 μm).
[0520] Various evaluation results of the resin film B-12 are as follows.
[0521] Relative dielectric constant: 3.0, dielectric loss tangent: 0.0040, CTE (TD): 42ppm / K, CTE (MD): 30ppm / K, humidified solder heat resistance: good
[0522] [Example B-13]
[0523] 24.6 g of particle B-2 was added to 50 g of DMAc solution containing 50 wt% of LCP B-3 fine powder, and after stirring, 10 g of LCP B-1 in shape B-1 was added, and DMAc was added to dilute and stir in such a way that the total solid content concentration became 50 wt%, thereby preparing LCP varnish B-1. Regarding the volume basis content of the total solid content in the LCP varnish B-1, LCP B-1 was 20%, and particle B-2 was 30%.
[0524] The prepared LCP varnish B-1 was cast onto an electrolytic copper foil (12 μm) and dried at 130° C. for 3 minutes. Thereafter, a stepwise heat treatment was performed from 155° C. to 340° C. to prepare a copper-clad laminate B-13. Furthermore, the copper foil was etched to prepare a resin film B-13 (thickness: 45 μm).
[0525] Various evaluation results of the resin film B-13 are as follows.
[0526] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0015, CTE (TD): 40ppm / K, CTE (MD): 38ppm / K
[0527] [Comparative Example B-1]
[0528] A copper-clad laminate B-14 and a resin film B-14 (thickness: 50 μm) were prepared in the same manner as in Example B-1, except that the particles B-1 and the LCP B-1 of the shape B-1 were not added.
[0529] The various evaluation results of the resin film B-14 and the copper-clad laminate B-14 are as follows.
[0530] Relative dielectric constant: 2.6, dielectric loss tangent: 0.0019, CTE (TD): 150ppm / K, CTE (MD): 150ppm / K, peel strength: 1.3kN / m, humidified solder heat resistance: good
[0531] [Comparative Example B-2]
[0532] A copper-clad laminate B-15 and a resin film B-15 (thickness: 49 μm) were prepared in the same manner as in Example B-3 except that LCP B-1 of shape B-1 was not added.
[0533] Various evaluation results of the resin film B-15 are as follows.
[0534] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0013, CTE (TD): 90ppm / K, CTE (MD): 90ppm / K, humidified solder heat resistance: good
[0535] [Comparative Example B-3]
[0536] A copper-clad laminate B-16 and a resin film B-16 (thickness: 48 μm) were prepared in the same manner as in Example B-6, except that the LCP B-1 of the shape B-1 was not added.
[0537] Various evaluation results of the resin film B-16 are as follows.
[0538] Relative dielectric constant: 2.9, dielectric loss tangent: 0.0020, CTE (TD): 72ppm / K, CTE (MD): 72ppm / K, humidified solder heat resistance: good
[0539] [Comparative Example B-4]
[0540] A copper-clad laminate B-17 and a resin film B-17 (thickness: 53 μm) were prepared in the same manner as in Example B-7, except that the LCP B-1 of the shape B-1 was not added.
[0541] Various evaluation results of the resin film B-17 are as follows.
[0542] Relative dielectric constant: 2.8, dielectric loss tangent: 0.0016, CTE (TD): 129ppm / K, CTE (MD): 129ppm / K, humidified solder heat resistance: good
[0543] [Reference Example B-1]
[0544] A copper-clad laminate B-18 and a resin film B-18 (thickness: 63 μm) were prepared in the same manner as in Example B-2 except that the particles B-1 were not added.
[0545] Various evaluation results of the resin film B-18 are as follows.
[0546] Relative dielectric constant: 1.9, dielectric loss tangent: 0.0017, CTE (TD): 120ppm / K, CTE (MD): 16ppm / K, humidified solder heat resistance: good
[0547] In addition to the above, various measurements and evaluations in the following examples were performed as follows.
[0548] [Evaluation of Dielectric Properties]
[0549] <Liquid crystal polymer particles>
[0550] A dimethylacetamide dispersion of liquid crystal polymer particles adjusted to 30 wt% solid content was applied to the smooth surface of the copper foil and dried at 120°C for 10 minutes. Thereafter, the temperature was gradually raised from 200°C to 360°C over 10 minutes to etch and remove the copper foil of the obtained laminate, thereby obtaining a liquid crystal polymer film.
[0551] Using a vector network analyzer (manufactured by Keysight Technologies, trade name: Vector Network Analyzer E8363C) and a separated dielectric resonator (SPDR resonator), the obtained liquid crystalline polymer film was placed under temperature: 23°C and humidity: 50% for 24 hours, and then the relative dielectric constant and dielectric loss tangent at a frequency of 10 GHz were measured.
[0552] [Volume average particle size D 50 Determination of
[0553] The volume average particle size of the resin particles was measured by a laser diffraction-scattering measurement method using water as a dispersion medium and a particle refractive index of 1.54 using a laser diffraction-scattering measurement apparatus (manufactured by Malvern, trade name: Master Sizer 3000).
[0554] The abbreviations used in Examples and Comparative Examples represent the following compounds.
[0555] LCP C-1: Liquid crystal polymer with polyester structure, melting point (Tm): 350°C, true specific gravity: 1.4, relative dielectric constant: 3.1, dielectric loss tangent: 0.0010
[0556] LCP C-2: Liquid crystal polymer with polyester structure, melting point (Tm): 330°C, true specific gravity: 1.4, relative dielectric constant: 3.4, dielectric loss tangent: 0.0020
[0557] Shape C-1: short fiber, average length of long axis: 0.5 mm, average length of short axis: 28 μm, manufacturing method: melt spinning and cutting
[0558] Shape C-2: short fiber, average length of long axis: 1 mm, average length of short axis: 28 μm, manufacturing method: melt spinning and cutting
[0559] Particle C-1: Liquid crystal polymer with polyester structure, melting point (Tm): 320°C, true specific gravity: 1.4, relative dielectric constant: 3.4, dielectric loss tangent: 0.0008, D 50 : 10μm, irregular shape
[0560] Particle C-2: Liquid crystal polymer with polyester structure, melting point (Tm): 325°C, true specific gravity: 1.4, relative dielectric constant: 3.4, dielectric loss tangent: 0.0007, D 50 : 5μm, irregular shape
[0561] (Synthesis Example C-1 to Synthesis Example C-3)
[0562] Polyimide solution C-1, polyimide solution C-2, and polyimide solution C-3 were prepared in the same manner as in Synthesis Example A-1, Synthesis Example A-2, and Synthesis Example A-3, respectively.
[0563] (Synthesis Example C-4 and Synthesis Example C-5)
[0564] Polyamic acid solution C-1 and polyamic acid solution C-2 were prepared in the same manner as in Synthesis Example B-4 and Synthesis Example B-5, respectively.
[0565] [Example C-1]
[0566] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution C-1 obtained in Synthesis Example C-1, 11.7 g of particles C-1 were added, and after stirring, 11.7 g of LCP C-1 in shape C-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish C-1. Regarding the volume-based content of the total solid content in the polyimide varnish C-1, LCP C-1 was 20%, and particles C-1 was 20%.
[0567] The prepared polyimide varnish C-1 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and then treated at 160°C for 1 hour to prepare a copper-clad laminate C-1. The copper foil was then etched to prepare a resin film C-1 (thickness: 129 μm).
[0568] The various evaluation results of the resin film C-1 and the copper-clad laminate C-1 are as follows.
[0569] Relative dielectric constant: 1.8, dielectric loss tangent: 0.0015, CTE (TD): 90ppm / K, CTE (MD): 14ppm / K, peel strength: 1.3kN / m, humidified solder heat resistance: good
[0570] [Example C-2]
[0571] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution C-1 obtained in Synthesis Example C-1, 35.0 g of particles C-1 were added, and after stirring, 17.5 g of LCP C-1 in shape C-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish C-2. Regarding the volume basis content of the total solid content in the polyimide varnish C-2, LCP C-1 was 20%, and particles C-1 was 40%.
[0572] The prepared polyimide varnish C-2 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and then treated at 160°C for 1 hour to prepare a copper-clad laminate C-2. The copper foil was then etched to prepare a resin film C-2 (thickness: 143 μm).
[0573] Various evaluation results of the resin film C-2 are as follows.
[0574] Relative dielectric constant: 1.9, dielectric loss tangent: 0.0013, CTE (TD): 64ppm / K, CTE (MD): 7ppm / K, humidified solder heat resistance: good
[0575] [Example C-3]
[0576] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution C-1 obtained in Synthesis Example C-1, 11.7 g of particles C-2 were added, and after stirring, 11.7 g of LCP C-1 in shape C-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish C-3. Regarding the volume basis content of the total solid content in the polyimide varnish C-3, LCP C-1 was 20%, and particles C-2 was 20%.
[0577] The prepared polyimide varnish C-3 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and treated at 160°C for 1 hour to prepare a copper-clad laminate C-3. The copper foil was then etched to prepare a resin film C-3 (thickness: 127 μm).
[0578] Various evaluation results of the resin film C-3 are as follows.
[0579] Relative dielectric constant: 1.9, dielectric loss tangent: 0.0015, CTE (TD): 96ppm / K, CTE (MD): 7ppm / K, humidified solder heat resistance: good
[0580] [Example C-4]
[0581] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution C-2 obtained in Synthesis Example C-2, 35.0 g of particles C-1 were added, and after stirring, 17.5 g of LCP C-1 in shape C-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish C-4. Regarding the volume basis content of the total solid content in the polyimide varnish C-4, LCP C-1 was 20%, and particles C-1 was 40%.
[0582] The prepared polyimide varnish C-4 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and treated at 160°C for 1 hour to prepare a copper-clad laminate C-4. The copper foil was then etched to prepare a resin film C-4 (thickness: 122 μm).
[0583] Various evaluation results of the resin film C-4 are as follows.
[0584] Relative dielectric constant: 1.9, dielectric loss tangent: 0.0012, CTE (TD): 60ppm / K, CTE (MD): 15ppm / K
[0585] [Example C-5]
[0586] 1.1 g of N-12 as a crosslinking agent was mixed into 100 g of the polyimide solution C-3 obtained in Synthesis Example C-3, 35.0 g of particles C-1 were added, and after stirring, 17.5 g of LCP C-1 in shape C-1 was added, and xylene was added to dilute and stir in such a way that the total solid content concentration became 45% by weight, thereby preparing polyimide varnish C-5. Regarding the volume-based content of the total solid content in the polyimide varnish C-5, LCP C-1 was 20%, and particles C-1 was 40%.
[0587] The prepared polyimide varnish C-5 was cast onto an electrolytic copper foil (12 μm), dried at 80°C for 20 minutes, and then treated at 160°C for 1 hour to prepare a copper-clad laminate C-5. The copper foil was further etched to prepare a resin film C-5 (thickness: 90 μm).
[0588] The various evaluation results of the resin film C-5 and the copper-clad laminate C-5 are as follows.
[0589] Relative dielectric constant: 2.0, dielectric loss tangent: 0.0014, CTE (TD): 55ppm / K, CTE (MD): 5ppm / K, peel strength: 1.5kN / m, humidified solder heat resistance: good
[0590] [Example C-6]
[0591] 5 g of particles C-1 were added to 100 g of the polyamic acid solution C-1 obtained in Synthesis Example C-4, and after stirring, 2.5 g of LCP C-1 in shape C-2 was added, and DMAc was added to dilute and stir in a manner such that the total solid content concentration became 20% by weight, thereby preparing polyamic acid varnish C-1. Regarding the volume-based content of the total solid content in the polyamic acid varnish C-1, LCP C-1 was 10%, and particles C-1 was 20%.
[0592] The prepared polyamic acid varnish C-1 was cast onto an electrolytic copper foil (12 μm) and dried at 130° C. for 3 minutes. Thereafter, a stepwise heat treatment was performed from 155° C. to 360° C. for imidization to prepare a copper-clad laminate C-6. Furthermore, the copper foil was etched to prepare a resin film C-6 (thickness: 52 μm).
[0593] Various evaluation results of the resin film C-6 are as follows.
[0594] Relative dielectric constant: 2.7, dielectric loss tangent: 0.0027, CTE (TD): 15ppm / K, CTE (MD): 5ppm / K
[0595] [Example C-7]
[0596] 5 g of particles C-2 were added to 100 g of the polyamic acid solution C-2 obtained in Synthesis Example C-5, and after stirring, 2.5 g of LCP C-2 in shape C-2 was added, and DMAc was added to dilute and stir in a manner such that the total solid content concentration became 15% by weight, thereby preparing polyamic acid varnish C-2. Regarding the volume-based content of the total solid content in the polyamic acid varnish C-2, LCP C-2 was 10%, and particles C-2 was 20%.
[0597] The prepared polyamic acid varnish C-2 was cast onto an electrolytic copper foil (12 μm) and dried at 130° C. for 3 minutes. Thereafter, a stepwise heat treatment was performed from 155° C. to 360° C. for imidization to prepare a copper-clad laminate C-7. Furthermore, the copper foil was etched to prepare a resin film C-7 (thickness: 45 μm).
[0598] Various evaluation results of the resin film C-7 are as follows.
[0599] Relative dielectric constant: 2.7, dielectric loss tangent: 0.0039, CTE (TD): 30ppm / K, CTE (MD): 28ppm / K
[0600] [Comparative Example C-1]
[0601] Copper-clad laminate C-8 and resin film C-8 (thickness: 50 μm) were prepared in the same manner as in Example C-1, except that particles C-1 and LCP C-1 of shape C-1 were not added.
[0602] The various evaluation results of the resin film C-8 and the copper-clad laminate C-8 are as follows.
[0603] Relative dielectric constant: 2.6, dielectric loss tangent: 0.0019, CTE (TD): 150ppm / K, CTE (MD): 150ppm / K, peel strength: 1.3kN / m, wet solder heat resistance: good
[0604] [Comparative Example C-2]
[0605] Copper-clad laminate C-9 and resin film C-9 (thickness: 45 μm) were prepared in the same manner as in Example C-1, except that the amount of particles C-1 added was 15 g and LCP C-1 of shape C-1 was not added.
[0606] The various evaluation results of the resin film C-9 and the copper-clad laminate C-9 are as follows.
[0607] Relative dielectric constant: 2.9, dielectric loss tangent: 0.0017, CTE (TD): 116ppm / K, CTE (MD): 116ppm / K, peel strength: 1.3kN / m, heat resistance of humidified solder: good
[0608] [Comparative Example C-3]
[0609] A copper-clad laminate C-10 and a resin film C-10 (thickness: 50 μm) were prepared in the same manner as in Comparative Example C-2, except that the particles C-1 were replaced with the particles C-2.
[0610] Various evaluation results of the resin film C-10 are as follows.
[0611] Relative dielectric constant: 2.9, dielectric loss tangent: 0.0017, CTE (TD): 110ppm / K, CTE (MD): 110ppm / K, humidified solder heat resistance: good
[0612] [Reference Example C-1]
[0613] Copper-clad laminate C-11 and resin film C-11 (thickness: 63 μm) were prepared in the same manner as in Example C-1 except that the particles C-1 were not added.
[0614] Various evaluation results of the resin film C-11 are as follows.
[0615] Relative dielectric constant: 1.9, dielectric loss tangent: 0.0017, CTE (TD): 120ppm / K, CTE (MD): 16ppm / K, humidified solder heat resistance: good
[0616] As mentioned above, although embodiment of this invention was described in detail for the purpose of illustration, this invention is not limited to the said embodiment, and various deformation|transformation is possible.
Claims
1. A resin composition comprising: The following components (A), (B), and (C): (A) a liquid crystal polymer filler having anisotropic shape and wherein X / Y is 2.5 or more when the average length of the major axis is X and the average length of the shortest minor axis among axes orthogonal to the major axis is Y; and (B) a matrix polymer; and (C) Particulate thermoplastic resin filler.
2. The resin composition according to claim 1, wherein The component (A) is a fibrous liquid crystal polymer filler.
3. The resin composition according to claim 2, wherein The total content of the fillers of the components (A) and (C) is within a range of 10 to 90 volume % and the content of the component (B) is within a range of 10 to 90 volume % based on the solid content in the resin composition.
4. The resin composition according to claim 2, wherein The ratio L / D of the average length L of the major axis of the fibrous liquid crystal polymer filler as the component (A) to the average diameter D of the minor axis perpendicular to the major axis is 2.5 or more.
5. The resin composition according to claim 4, wherein The fibrous liquid crystal polymer filler of the component (A) has an average length L of its major axis in the range of 0.1 mm to 5 mm, and an average diameter D of its minor axis in the range of 5 μm to 50 μm.
6. The resin composition according to claim 2, wherein The melting point of the fibrous liquid crystal polymer filler of the component (A) is 290° C. or higher.
7. The resin composition according to claim 2, wherein The content of the fibrous liquid crystal polymer filler of the component (A) is in the range of 5 volume % to 60 volume % relative to the solid content of the resin composition.
8. The resin composition according to claim 2, wherein The volume average particle size D of the particulate thermoplastic resin filler of the component (C) is 50 It is in the range of 1 μm to 100 μm.
9. The resin composition according to claim 2, wherein The particulate thermoplastic resin filler of the component (C) is one or more particles selected from the group consisting of thermoplastic polyimide, liquid crystal polymer and fluororesin.
10. The resin composition according to claim 2, wherein The content of the component (C) is within a range of 20% to 80% by volume relative to the solid content in the resin composition.
11. The resin composition according to claim 2, wherein The ratio of the content of the fibrous liquid crystal polymer filler of the component (A) to the content of the component (C) [component (A) / component (C)] is within a range of 0.1 to 10 on a volume basis.
12. The resin composition according to claim 2, wherein The average diameter D of the minor axis of the fibrous liquid crystal polymer filler of the component (A) relative to the volume average particle diameter D of the particulate thermoplastic resin filler of the component (C) 50 The ratio [D / D 50 ] is in the range of 1 to 50.
13. The resin composition according to claim 2, wherein The average length L of the major axis of the fibrous liquid crystal polymer filler of the component (A) relative to the volume average particle size D of the particulate thermoplastic resin filler of the component (C) is 50 The ratio [L / D 50 ] is in the range of 10 to 1000.
14. The resin composition according to claim 2, wherein The component (B) is at least one selected from thermoplastic polyimide, liquid crystal polymer and fluororesin.
15. The resin composition according to claim 2, wherein The component (B) is a polyimide using a diamine component as a raw material, wherein the diamine component in the polyimide contains a dimer diamine composition having as a main component a dimer diamine in which both terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups in an amount of 30 mol % or more based on all diamine components.
16. A resin film having a single or multiple resin layers, wherein: At least one of the resin layers is a filler-containing resin layer formed using the resin composition according to claim 2 .
17. The resin film according to claim 16, wherein The filler-containing resin layer, after being conditioned at a constant temperature and humidity of 23° C. and 50% RH for 24 hours, has a relative dielectric constant of 3 or less and a dielectric loss tangent of 0.003 or less at 10 GHz as measured by a separation dielectric resonator.
18. The resin film according to claim 16, wherein The filler-containing resin layer has an absolute value of an average thermal expansion coefficient in the longitudinal direction at 10° C. to 20° C. of 50 ppm / K or less, and an absolute value of an average thermal expansion coefficient in the transverse direction of 100 ppm / K or less.
19. A metal-clad laminate comprising a single-layer or multi-layer insulating resin layer and a metal layer laminated on at least one side of the insulating resin layer, characterized in that: At least one layer constituting the insulating resin layer includes the resin film according to claim 16 .
20. A printed wiring board comprising: The invention comprises a single-layer or multi-layer insulating resin layer and a circuit wiring layer laminated on at least one side of the insulating resin layer, characterized in that: At least one layer constituting the insulating resin layer includes the resin film according to claim 16 .
Citation Information
Patent Citations
Variable equalizer
JP1987095013A
Composite film comprising low-permittivity resin and p-directing polyamide, prepreg thereof and use thereof
JP1998338809A
Electrical insulating resin composition and printed wiring board
JP1999273456A
Resin laminate plate for printed wiring board
JP2002064254A